Accelerated climate-induced risks of nitrogen-loss from agricultural catchments: Empirical modelling of extreme weather events using climate change scenarios - G. Ezzati; P. Mellander; J. Ortega; B. Fan; C. Murphy (Water Research, 2027)

Placental toxic metal concentrations and preterm birth: Modification by social stressors - Ruohan Liao; Adriana C. Vidal; James Harrington; John Thorp; David Skaar; Yukun Liu; Susan K. Murphy; David W. Sosnowski; Sara B. Johnson; Gang Peng; Jung-Ying Tzeng; Cathrine Hoyo (Reproductive Toxicology, 2026)

GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

The effect of form on equine salt intake - B. Murphy; D.N. Catalano (Journal of Equine Veterinary Science, 2026)

Changes in suspended sediment concentration along tidal rivers of the Chesapeake Bay: the tidal freshwater “sediment shadow” - Gregory B. Noe; Rebecca R. Murphy; Ken W. Krauss (Estuarine, Coastal and Shelf Science, 2026)

“Persistent ecological impacts related to West Nile virus revealed using community science and vector surveillance data” - Brock Geary; Adam C. Smith; Lisa Williams; Sean P. Murphy; Brandon P.M. Edwards; Nicole L. Michel; Timothy D. Meehan; Roderick B. Gagne (Biological Conservation, 2026)

Impacts of Quaternary Climate History on the Biogeography of Specialized Butterflies in the Great Basin of North America - Sarah B. Bialik; Joseph S. Wilson; Michelle Sneck; Dennis D. Murphy; James A. Fordyce; Katherine L. Bell; Matthew L. Forister; Chris C. Nice (Journal of Biogeography, 2026)
Aim Dramatic Quaternary climate fluctuations impacted the evolutionary history and contemporary biogeography of many residents of the Great Basin Desert of western North America. This study investigates the historical biogeographic processes that shaped the contemporary distribution of genetic variation in a polytypic group of specialized butterflies that are residents of unique dune and playa habitats. Many of the subspecies are considered to be threatened and this study uses high‐resolution SNP data to understand their history and quantify patterns of differentiation to inform conservation. Location Great Basin, western North America. Taxon The pallid dotted blue butterfly complex ( Euphilotes pallescens , Lycaenidae). Methods We constructed reduced‐representation genomic libraries to generate population genomics data that were used in clustering, ordination, and phylogenetic analyses. Pairwise differentiation between localities was quantified and the relationship between genomic differentiation and geography was analysed using a linear model. In addition, an estimated effective migration surface illustrated geographic patterns of genomic variation. Results Euphilotes pallescens populations were clearly differentiated from congeneric species and several subspecies, especially in the northwestern portion of the sampled range, were identifiable from genomic variation. When geographic distance was controlled, genetic differentiation was greatest between populations of Eu. pallescens compared to congeners, and within Eu. pallescens , northwestern populations were more differentiated than southern populations. The estimated effective migration surface also showed greater areas of reduced gene flow in the northwestern region. Main Conclusions Euphilotes pallescens comprises isolated populations on dune habitats in the Great Basin. Populations in the northwestern region are especially isolated and their patterns of genetic variation are consistent with the history of climate change and ancient pluvial lakes that occupied much of this region at intervals during the Quaternary. These butterflies are members of unique, localized communities whose persistence requires protections from anthropogenic threats, especially habitat loss including from recreation and off‐road vehicles in sensitive habitats.

Genetic sibship and parental reconstruction shed light on the mating systems and larval dispersal of an iconic Australian freshwater fish - J. E. O'Dwyer; K. A. Harrisson; Z. Tonkin; J. Lyon; B. Zampatti; W. Koster; S. Raymond; D. Dawson; C. Bice; N. Murphy (Journal of Fish Biology, 2026)
Mating systems shape the population dynamics of species, influencing attributes such as effective population size and population persistence. Traditionally, genetic analysis of mating systems includes the genotyping of putative parents to determine parentage. However, for cryptic or migratory species, and those with large populations, comprehensive sampling of adults is often not feasible. One underutilised alternative is to reconstruct parental genotypes from sibling relationships (i.e., sibship). We develop a generalisable sibship workflow for delineating types of first‐ and second‐ order kinship classifications in medium‐/low‐density SNP marker datasets and apply it to investigate the mating systems of the iconic Australian freshwater fish, Murray cod ( Maccullochella peelii ) using larvae collected over five breeding seasons and three breeding locations. We explored the relative occurrences of monogamous and polygamous pairings within and across breeding seasons along with larval dispersal patterns, and connectivity among breeding locations. Whilst monogamy was the most common mating strategy identified within each breeding season, only a single instance of multi‐year pair‐bonding was detected. Across seasons, 18% of putative adults were redetected and bred with a new partner, and within‐season polygynandry was detected in all three study reaches. Larval kin were found up to 71 km apart over only a few weeks of sampling and kin pairs were detected across two of the breeding locations (120–150 km apart) over seasons. Relatively high rates of polygynandry in wild Murray cod may promote the maintenance of genetic diversity and reduce vulnerability to recruitment disruptions in a climatically variable river system. Our study provides a valuable case study demonstrating that sibship analysis can provide insights into mating systems and dispersal potential of species where sampling adults is logistically difficult compared with collecting offspring.

HDR brachytherapy postal audit across Australia and New Zealand with in air jig - Emily Murphy; David Little; Rachael Wilks; Scott B. Crowe; Tanya Kairn (Physical and Engineering Sciences in Medicine, 2026)

Non‐native pink salmon Oncorhynchus gorbuscha carcasses benefit native benthic macroinvertebrates - Hui Wei; Gordon H. Copp; Rasmus B. Lauridsen; Tea Bašić; Phil I. Davison; John F. Murphy; James L. Pretty; Michał E. Skóra; Gabriela Zemelka; John Iwan Jones (Journal of Fish Biology, 2026)
The invasion of the North Atlantic by pink salmon Oncorhynchus gorbuscha has raised concerns regarding their impact on coastal rivers. Although the influence of marine‐derived nutrients from returning adult O. gorbuscha on rivers in their native range has received much attention, the ecological consequences of invasive O. gorbuscha for ecosystems outside the native range are largely unknown. To investigate the impact on the density and community structure of benthic macroinvertebrates, O. gorbuscha carcasses were added to 12 experimental channels for 60 days at three treatment levels (control, no carcass; low and high, loading rates). Stable isotopes of carbon (δ 13 C) and nitrogen (δ 15 N) were used to determine if nutrients from carcasses were incorporated into native biota. The density of macroinvertebrates increased close to the carcasses in the high‐addition treatment, suggesting aggregation. Furthermore, macroinvertebrates had a higher δ 15 N near to the carcasses in the low‐ and high‐addition treatments after 30 days, indicating uptake from the carcasses. The higher δ 15 N of willow moss Fontinalis antipyretica in carcass‐addition treatments indicated that primary producers could also assimilate nutrients from the decomposition of carcasses. Whilst the addition of carcasses resulted in the increased density of small individuals of macroinvertebrates, this did not propagate to changes in community composition in this relatively short experiment. Overall, the results suggest that native biota might benefit from the marine‐derived nutrients transported to streams by invasive O. gorbuscha , however, the long‐term effects of such nutrient/energy subsidies on receiving ecosystems require further investigation.

Diversity and functional group composition drive biogeographic patterns in marine biogenic structural complexity - Dean S. Janiak; Matthew A. Whalen; David R. Branson; Soledad Álvarez; Gail V. Ashton; Nicholas M. Bartkowiak; Simon J. Brandl; João Canning‐Clode; Jordan M. Casey; Max C. N. Castorani; Carolina César‐Ávila; Rachel Collin; et al. (Ecology, 2026)
Biogenic structural complexity is a key driver of biodiversity and ecosystem functioning, yet its ecological and environmental determinants remain poorly understood across broad biogeographic scales. Here, we conducted standardized 90‐day field experiments at 16 coastal sites, spanning a 41‐degree latitudinal gradient, using naturally assembled marine fouling communities on settlement panels. We measured rugosity as our metric of biogenic structural complexity and modeled its relationship with species richness, community composition, community growth rates, and abiotic conditions (salinity and temperature). Species richness increased with temperature and salinity and declined with latitude, with more diverse communities exhibiting greater biogenic complexity due to increased morphological variation. At high‐latitude sites, low‐diversity communities dominated by arborescent bryozoans also had increased complexity. Structural equation models showed that abiotic conditions influenced growth and composition, which in turn shaped complexity. Warmer, saltier sites promoted richness‐driven complexity, while colder conditions favored structurally important dominant taxa. We found that biodiversity is important not only as a beneficiary of complexity but also as a contributor to complexity itself within fouling communities. Our results also demonstrate that both species richness and functional group identity regulate biogenic complexity across environmental gradients, underscoring biodiversity's role in supporting ecosystem structure and resilience in the face of increasing global change. Understanding these relationships is essential for biodiversity conservation and the management of marine ecosystems facing increasing anthropogenic pressures.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Increasing Efficiency of Detection and Validation of Baleen Whale Call Presence on Large Acoustic Datasets: A Case Study Using Sei Whale Downsweeps Recorded in Atlantic Canada - Gabrielle F. Macklin; Hilary B. Moors‐Murphy; Marty L. Leonard (Marine Mammal Science, 2026)
As passive acoustic monitoring (PAM) datasets expand, studies increasingly use automated detectors to analyze baleen whale presence. However, detector errors like false positives (impacting precision, P; proportion of detected calls that are correct), and false negatives (impacting recall, R; proportion of available calls successfully detected) necessitate manual validation. Here, we demonstrate a tiered detection and validation approach to improve efficiency in sei whale ( Balaenoptera borealis ) call presence analysis that aims to maximize R while removing false positives. Using two detectors on eastern Canadian datasets, we tested multiple parameter settings, selecting one tier that captured only high‐quality calls (High‐P), one tier that captured most calls present but included more false positives (High‐R), and one tier that balanced the P and R values (Mid). To assess daily call presence, validation proceeded sequentially across tiers from High‐P to Mid to High‐R. For each subsequent tier, detections were only reviewed from days in which sei whale calls had not yet been confirmed. For both detectors, using this tiered approach reduced the overall manual validation effort (number of detections reviewed) when compared to validating the highest recall original outputs alone. This efficient strategy maintains accuracy in PAM studies and could be used for other species.

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Twice daily top-dressing of 3-nitrooxypropanol as a strategy to reduce enteric methane emissions in pregnant non-lactating dairy cows consuming grass silage - B. Lahart; L. Shalloo; W. Flynn; V. Glevarec; J.P. Murphy; N. Walker; H. Costigan (Animal Feed Science and Technology, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Seascape diversity and configuration shape habitat selection across multiple coastal ecosystems - Jesse D. Mosman; Hayden P. Borland; Ashley J. Rummell; Christopher J. Henderson; Sam Allan; Alec Bannam; Stacy L. Bierwagen; Michael J. Bradley; Alex B. Carter; Daniela M. Ceccarelli; Robert Coles; Michael J. Emslie; et al. (Biological Conservation, 2026)

Fine-scale patterns and drivers of ploidy state in lentic and lotic macrophyte assemblages across the world - Tatiana Lobato-de Magalhães; Kevin Murphy; Thomas A. Davidson; Jorge García-Girón; Andrey Efremov; Victor Chepinoga; Eugenio Molina-Navarro; Celeste Franceschini; Roger P. Mormul; Hui Fu; Rossano Bolpagni; Juri Nascimbene; et al. (Aquatic Botany, 2026)

Gas and Water Relative Permeability in Hydrate Systems - David DiCarlo; Zachary W. Murphy; Kehua You; Peter B. Flemings (Transport in Porous Media, 2025)

Quantifying microplastic fluvial flux from a coastal watershed—A microplastic rating curve approach - Clare Murphy-Hagan; Andrew B. Gray; Samiksha Singh; Hannah Hapich; Win Cowger (Journal of Environmental Management, 2025)

P18-82 validation of scinora media for the culture of airway relevant cell lines: progress towards an animal-free airway model for nanomaterial toxicity testing - K. Mcallister; F. Murphy; B. Thalmann (Toxicology Letters, 2025)

Life and death of a sinter archive: Evolution of siliceous hot-spring deposits (Holocene) on the dynamic Paeroa Fault at Te Kopia, Taupō Volcanic Zone, New Zealand - M.C. Rowe; K.A. Campbell; A. Hamilton; Y. Jiang; J. Pelser; B. Murphy; R. Martin; K.M. Mackenzie; D.A. Stallard; B. Lyon; A. Langendam; E.E. Nersezova; et al. (Journal of Volcanology and Geothermal Research, 2025)

Early pyroxene crystallisation deep below mid-ocean ridges - Teresa Ubide; David T. Murphy; Robert B. Emo; Michael W.M. Jones; Marco A. Acevedo Zamora; Balz S. Kamber (Earth and Planetary Science Letters, 2025)

Scaling up eco-engineering: The role of topographic complexity and spatial variability in shaping biodiversity on coastal structures - Charlotte H. Clubley; Antony M. Knights; Jessica Allen; David T. Bilton; Andy Foggo; Mick E. Hanley; James Murphy; Louisa E. Wood; Louise B. Firth (Science of The Total Environment, 2025)

Outcome measurement instruments used to measure diet-related outcomes in infancy: A scoping review - Karen Matvienko-Sikar; Moira Duffy; Eibhlín Looney; Reindolf Anokye; Catherine S. Birken; Vicki Brown; Darren Dahly; Ann S. Doherty; Dimity Dutch; Rebecca Golley; Brittany J. Johnson; Patricia Leahy-Warren; et al. (Appetite, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Evaluating the SEND eHealth Application to Improve Patients’ Secure Message Writing - Jordan M. Alpert; Tithi B. Amin; Zhang Zhongyue; Merry Jennifer Markham; Martina Murphy; Carma L. Bylund (Journal of Cancer Education, 2025)
Secure messaging (SM) is an important aspect of communication for patients with cancer. SM fosters patient-clinician communication and helps patients with symptom management and treatment support. However, patients are uncertain about how to phrase messages appropriately and have expressed the need for guidance. In response, we designed a user-centered, web-based application named SEND The application focuses on specificity, expression, needs, and directness through interactive video tutorials and quizzes. Our objective was to comprehensively evaluate SEND based on its levels of engagement, satisfaction, acceptability, and appropriateness. We recruited 101 patients with various cancer diagnoses to use SEND and then fill out a survey 1 to 2 weeks later about their experience. Patients’ mean age was 64 years; most were male (55%), white (83%), diagnosed with cancer in 2020 with high levels of self-efficacy, and 51% had a bachelor’s degree or higher. 65% were engaged in the application, and respondents spent an average of 15 min interacting with SEND Satisfaction was 90.4%, 85.4% found it acceptable, and 88.6% appropriate. There were no statistically significant differences across age, sex, race, education, or year of diagnosis. Results underscore the potential of eHealth interventions, like SEND, in enhancing patient-clinician communication in cancer care. By empowering patients with effective message-writing techniques, SEND has the potential to improve the quality of SM, which can lead to faster response times and more patient-centered responses.

Otolith and Genomic Data Reveal Temporal Insights Into Stocking Across a Large River Basin in a Mobile, Long‐Lived Australian Freshwater Fish Species - Katherine A. Harrisson; Luciano B. Beheregaray; Christopher M. Bice; Emily J. Booth; Chris J. Brauer; Gavin L. Butler; David Dawson; Olga Dudchenko; Benjamin G. Fanson; Graeme Hackett; Annique Harris; Matthew J. Jones; et al. (Molecular Ecology, 2025)
Freshwater ecosystems and their biota are under increasing pressure from anthropogenic stressors. In response to declining fish stocks, hatchery and stocking programmes are widely implemented as core components of restoration and management strategies, with positive outcomes for some wild populations. Despite this, stocking remains contentious due to potential genetic and ecological risks to wild populations. Monitoring and evaluation of stocking outcomes are critical to ensuring the long‐term sustainability of wild populations, but identification of stocked individuals post‐release remains a key challenge, particularly for mobile species. In this study, we combined otolith (natal origin and age) and genomic data to identify stocked individuals and evaluate the genetic implications of stocking for a culturally and socioeconomically important and mobile freshwater fish, golden perch Macquaria ambigua (family: Percichthyidae), across Australia's Murray–Darling Basin (MDB). We also generated a chromosome‐level genome assembly. Many close kin were detected across the MDB, increasing in prevalence over recent decades and mostly of hatchery origin. Rivers with many close kin were associated with low effective population sizes ( N e

“Hope at a better chance”: perspectives on genetic counseling and testing among black individuals with prostate cancer - Breanne Prindeville; Brittany M. Szymaniak; Samantha E. Greenberg; Adam B. Murphy; Ashley E. Ross; Debra Duquette (Journal of Community Genetics, 2025)

Microplastic characterization and transport mode —A flow-integrated approach to sampling urban waterways - Clare Murphy-Hagan; Andrew B. Gray; Samiksha Singh; Hannah Hapich; Win Cowger; Meredith E. Seeley; Kryss Waldschläger (Environmental Research, 2025)

Microplastic pollution in the water column and benthic sediment of the San Pedro Bay, California, USA - Samiksha Singh; Andrew B. Gray; Clare Murphy-Hagan; Hannah Hapich; Win Cowger; John Perna; Thai Le; Hinako Nogi; Bani Badwal; Karen McLaughlin; Fayçal Kessouri; Charles Moore; et al. (Environmental Research, 2025)

Ribwort plantain inclusion reduces nitrate leaching from grass-clover swards; A multi-year five soil study - Aoife Egan; Thomas Moloney; John B. Murphy; Patrick J. Forrestal (Agriculture, Ecosystems & Environment, 2025)

Environmental contaminants assessment for frequently harvested migratory waterfowl in the Northeast Atlantic flyway - David B. Dayan; Brenda J. Hanley; Joshua Stiller; Wayne Richter; Ian D. Gregg; Nate R. Huck; Min T. Huang; Theodore C. Nichols; Henry M. Spliethoff; Jesse C. Becker; Lisa A. Murphy; Krysten L. Schuler (Science of The Total Environment, 2025)

CO2 conversion using non-thermal plasmas: The path towards industrialisation - Yunxia Yang; Anthony B. Murphy (Current Opinion in Green and Sustainable Chemistry, 2025)

Ecological but Not Biological Traits of European Riverine Invertebrates Respond Consistently to Anthropogenic Impacts - James S. Sinclair; Rachel Stubbington; Ralf B. Schäfer; Libuše Barešová; Núria Bonada; Zoltán Csabai; J. Iwan Jones; Aitor Larrañaga; John F. Murphy; Petr Pařil; Marek Polášek; Jes J. Rasmussen; et al. (Global Ecology and Biogeography, 2024)
Aim To determine which riverine invertebrate traits respond consistently to anthropogenic impacts across multiple biogeographic regions. Location Europe. Time Period 1981–2021. Major Taxa Studied Riverine invertebrates. Methods We compiled a database of riverine invertebrate community time series for 673 sites across six European countries spanning six freshwater ecoregions. We compared trait responses to anthropogenic impacts (quantified as changes in ‘ecological quality’) among regions for seven ‘ecological’ traits, which reflect habitat preferences, and nine ‘biological’ traits (e.g., morphology or life history), which represent taxon‐specific attributes that can influence ecosystem processes. Results Four ecological traits (current, microhabitat, salinity and trophic preferences) and one biological trait (dispersal mode) responded consistently across regions. These responses were primarily driven by spatial differences among poorer to better quality sites. Responses to temporal changes in quality were comparable but less pronounced. Main Conclusions Consistent responses to anthropogenic impacts across multiple ecological traits indicate these traits may improve broader scale measurements, comparisons and predictions of community responses. However, we could not use ecological traits to identify the actions of specific stressors because multiple traits always responded as a group. Inconsistent responses across almost all biological traits indicated that these traits may be less predictive of impacts across regions. Predictions of how biological traits, and associated ecosystem processes, respond to anthropogenic impacts may be most effective at regional scales where responses are more consistent.

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

Failure Consequence Cost Analysis of Wave Energy Converters—Component Failures, Site Impacts, and Maintenance Interval Scenarios - Mitra Kamidelivand; Peter Deeney; Jimmy Murphy; José Miguel Rodrigues; Paula B. Garcia-Rosa; Mairead Atcheson Cruz; Giacomo Alessandri; Federico Gallorini (Journal of Marine Science and Engineering, 2024)
In the early stages of developing wave energy converter (WEC) projects, a quantitative assessment of component failure consequence costs is essential. The WEC types, deployment site features, and accessibility should all be carefully considered. This study introduces an operation and maintenance failure consequence cost (O&M-FC) model, distinct from conventional O&M models. The model is illustrated with case studies at three energetic Atlantic sites, each of which considers two types of generic floating WECs: a 300 kW point absorber (PA) with a hydraulic power-take-off (PTO) and a 1000 kW oscillating water column (OWC) with an air-wells-turbine PTO. This study compares 39 failure modes for PA and 27 for OWC in terms of direct repair costs and indirect lost production costs, examining the impact of location accessibility, capacity factors, and the mean annual energy production. The discussion revolves around the sensitive parameters. Recommendations for failure mitigations are presented, and the impact of planned maintenance (PM) during the operational phase is examined for 20 MW PA and OWC WEC projects. For a given WEC type, the method thoroughly evaluates how the location affects performance metrics. It offers a decision-making tool for determining optimal PM intervals to meet targets such as O&M costs, operating profit, or availability.

Persisting neurobehavioral consequences of daily or intermittent paternal cannabis administration in F1 and F2 Rats - Andrew B. Hawkey; Sarabesh Natarajan; Olivia Kelly; Anas Gondal; Corinne Wells; Michelle Louise Jones; Amir H. Rezvani; Susan K. Murphy; Edward D. Levin (NeuroToxicology, 2024)

Prenatal exposure to polycyclic aromatic hydrocarbons and executive functions at school age: Results from a combined cohort study - Yu Ni; Adam A. Szpiro; Christine T. Loftus; Tomomi Workman; Alexis Sullivan; Erin R. Wallace; Anne M. Riederer; Drew B. Day; Laura E. Murphy; Ruby H.N. Nguyen; Sheela Sathyanarayana; Emily S. Barrett; et al. (International Journal of Hygiene and Environmental Health, 2024)

Combining camera trap surveys and IUCN range maps to improve knowledge of species distributions - Cheng Chen; Alys Granados; Jedediah F. Brodie; Roland Kays; T. Jonathan Davies; Runzhe Liu; Jason T. Fisher; Jorge Ahumada; William McShea; Douglas Sheil; Jayasilan Mohd‐Azlan; Bernard Agwanda; et al. (Conservation Biology, 2024)
Reliable maps of species distributions are fundamental for biodiversity research and conservation. The International Union for Conservation of Nature (IUCN) range maps are widely recognized as authoritative representations of species’ geographic limits, yet they might not always align with actual occurrence data. In recent area of habitat (AOH) maps, areas that are not habitat have been removed from IUCN ranges to reduce commission errors, but their concordance with actual species occurrence also remains untested. We tested concordance between occurrences recorded in camera trap surveys and predicted occurrences from the IUCN and AOH maps for 510 medium‐ to large‐bodied mammalian species in 80 camera trap sampling areas. Across all areas, cameras detected only 39% of species expected to occur based on IUCN ranges and AOH maps; 85% of the IUCN only mismatches occurred within 200 km of range edges. Only 4% of species occurrences were detected by cameras outside IUCN ranges. The probability of mismatches between cameras and the IUCN range was significantly higher for smaller‐bodied mammals and habitat specialists in the Neotropics and Indomalaya and in areas with shorter canopy forests. Our findings suggest that range and AOH maps rarely underrepresent areas where species occur, but they may more often overrepresent ranges by including areas where a species may be absent, particularly at range edges. We suggest that combining range maps with data from ground‐based biodiversity sensors, such as camera traps, provides a richer knowledge base for conservation mapping and planning.

A Decade in Review: Trends in Female Authorship in Peer-Reviewed Toxicology Journals - Jennifer S. Love; George T. Loo; Lauren Murphy; Courtney Temple; Meghan B. Spyres; Alex F. Manini; Ayrn D. O’Connor (Journal of Medical Toxicology, 2024)

Climate and human mortality in Virginia, 2005–2020 - Robert E. Davis; Patrick C. Roney; Melanie M. Pane; Murphy C. Johnson; Hannah V. Leigh; William Basener; Amber L. Curran; Bryan DeMarcy; Jungyun Jang; Christian Schroeder; Pamela B. DeGuzman; Wendy M. Novicoff (Science of The Total Environment, 2023)

Science opportunities with solar sailing smallsats - Slava G. Turyshev; Darren Garber; Louis D. Friedman; Andreas M. Hein; Nathan Barnes; Konstantin Batygin; Michael E. Brown; Leroy Cronin; Artur R. Davoyan; Amber Dubill; T. Marshall Eubanks; Sarah Gibson; et al. (Planetary and Space Science, 2023)

Temporal and spatial evolution of the 2021 eruption in the Tajogaite volcano (Cumbre Vieja rift zone, La Palma, Canary Islands) from geophysical and geodetic parameter analyses - M. B. Benito; G. E. Alvarado; M. Marchamalo; J. G. Rejas; P. Murphy; R. Franco; D. Castro; C. Garcia-Lanchares; J. Sanchez (Natural Hazards, 2023)
The eruption of the Tajogaite volcano in 2021, in the Cumbre Vieja rift zone (La Palma, Canary Islands), is the most recent but also the most damaging and longest-lasting eruption on the island since historical records began. We analyzed geophysical parameters (seismicity, surface deformation, thermal anomalies, and volcanic activity) with the aim of reconstructing the temporal development of the magma plumbing system. The seismic sequence (> 9000 events, mbLg ≤ 5.0) can be grouped into nine distinct phases, which correspond to well-separated spatial clusters and distinct earthquake regimes. A strong premonitory thermal anomaly was calculated on July 2021 in the South of La Palma. The source of the magma was within the upper mantle (40–20 km depth). A second magma budget (< 15 km depth) indicated a short-term stagnation of alkaline magma within the lower crust, near the Moho. The outline of these earthquakes delineates the magma pathway. Just before and immediately after the eruption (phases 2 and 3), the high-frequency seismicity in the mantle disappeared completely, reappearing ten days after the eruption started. The pattern of deformation began before the eruption with a breakpoint around September 11, after which, deformation accelerated sharply, followed by stabilization in phase 3 and a decrease in the following phases. The level of deformation suggested that a shallow magma intrusion was established. Based on the historical eruptive pattern, it is possible to infer two possible hazard-forecast scenarios: (a) the volcano could enter a prolonged phase of tranquility for more than one century or, (b) a new eruption could occur between ca. 2045 and 2065, with a slightly shorter duration than this recent one. Therefore, if the more pessimistic scenario is assumed, appropriate territorial planning is required.

Insights into plasma-catalytic nitrogen fixation from catalyst microanalysis and chemical kinetics modelling - Jing Sun; Tianqi Zhang; Jungmi Hong; Rusen Zhou; Hassan Masood; Renwu Zhou; Anthony B. Murphy; Kostya Ken Ostrikov; Patrick J. Cullen; Emma C. Lovell; Rose Amal; Ali Rouhollah Jalili (Chemical Engineering Journal, 2023)

The faunal Ponto-Caspianization of central and western European waterways - Ismael Soto; Ross N. Cuthbert; Anthony Ricciardi; Danish A. Ahmed; Florian Altermatt; Ralf B. Schäfer; Gaït Archambaud-Suard; Núria Bonada; Miguel Cañedo-Argüelles; Zoltán Csabai; Thibault Datry; Jaimie T. A. Dick; et al. (Biological Invasions, 2023)
As alien invasive species are a key driver of biodiversity loss, understanding patterns of rapidly changing global species compositions depends upon knowledge of invasive species population dynamics and trends at large scales. Within this context, the Ponto-Caspian region is among the most notable donor regions for aquatic invasive species in Europe. Using macroinvertebrate time series collected over 52 years (1968–2020) at 265 sites across 11 central and western European countries, we examined the occurrences, invasion rates, and abundances of freshwater Ponto-Caspian fauna. We examined whether: (i) successive Ponto-Caspian invasions follow a consistent pattern of composition pioneered by the same species, and (ii) Ponto-Caspian invasion accelerates subsequent invasion rates. In our dataset, Ponto-Caspian macroinvertebrates increased from two species in 1972 to 29 species in 2012. This trend was parallelled by a non-significant increasing trend in the abundances of Ponto-Caspian taxa. Trends in Ponto-Caspian invader richness increased significantly over time. We found a relatively uniform distribution of Ponto-Caspian macroinvertebrates across Europe without any relation to the distance to their native region. The Ponto-Caspian species that arrived first were often bivalves (46.5% of cases), particularly Dreissena polymorpha , followed secondarily by amphipods (83.8%; primarily Chelicorophium curvispinum and Dikerogammarus villosus ) . The time between consecutive invasions decreased significantly at our coarse regional scale, suggesting that previous alien establishments may facilitate invasions of subsequent taxa. Should alien species continue to translocate from the Ponto-Caspian region, our results suggest a high potential for their future invasion success highly connected central and western European waters. However, each species’ population may decline after an initial ‘boom’ phase or after the arrival of new invasive species, resulting in different alien species dominating over time.

Organic ultraviolet filter mixture promotes bleaching of reef corals upon the threat of elevated seawater temperature - Tangtian He; Mirabelle M.P. Tsui; Anderson B. Mayfield; Pi-Jen Liu; Te-Hao Chen; Li-Hsueh Wang; Tung-Yung Fan; Paul K.S. Lam; Margaret B. Murphy (Science of The Total Environment, 2023)

Daily activity timing in the Anthropocene - Neil A. Gilbert; Kate A. McGinn; Laura A. Nunes; Amy A. Shipley; Jacy Bernath-Plaisted; John D.J. Clare; Penelope W. Murphy; Spencer R. Keyser; Kimberly L. Thompson; Scott B. Maresh Nelson; Jeremy M. Cohen; Ivy V. Widick; et al. (Trends in Ecology & Evolution, 2023)

Long-term trends in crayfish invasions across European rivers - Ismael Soto; Danish A. Ahmed; Ayah Beidas; Francisco J. Oficialdegui; Elena Tricarico; David G. Angeler; Giuseppe Amatulli; Elizabeta Briski; Thibault Datry; Alain Dohet; Sami Domisch; Judy England; et al. (Science of The Total Environment, 2023)

Fostering the Next Generation of Researchers: a Sustainable Mentoring Program for Early Career Toxicologists in Scientific Abstract Review - Mark B. Mycyk; Christine M. Murphy; Michael Chary; Peter R. Chai; Adrienne Dunavin; Alison Meyn; Maryann Mazer-Amirshahi (Journal of Medical Toxicology, 2023)

Multispecies swards outperform perennial ryegrass under intensive beef grazing - Shona Baker; Mary B. Lynch; Fionnuala Godwin; Tommy M. Boland; Alan K. Kelly; Alexander C.O. Evans; Paul N.C. Murphy; Helen Sheridan (Agriculture, Ecosystems & Environment, 2023)

Including imprecisely georeferenced specimens improves accuracy of species distribution models and estimates of niche breadth - Adam B. Smith; Stephen J. Murphy; David Henderson; Kelley D. Erickson (Global Ecology and Biogeography, 2023)
Aim Museum and herbarium specimen records are frequently used to assess the conservation status of species and their responses to climate change. Typically, occurrences with imprecise geolocality information are discarded because they cannot be matched confidently to environmental conditions and are thus expected to increase uncertainty in downstream analyses. However, using only precisely georeferenced records risks undersampling of the environmental and geographical distributions of species. We present two related methods to allow the use of imprecisely georeferenced occurrences in biogeographical analysis. Innovation Our two procedures assign imprecise records to the (1) locations or (2) climates that are closest to the geographical or environmental centroid of the precise records of a species. For virtual species, including imprecise records alongside precise records improved the accuracy of ecological niche models projected to the present and the future, especially for species with c . 20 or fewer precise occurrences. Using only precise records underestimated loss of suitable habitat and overestimated the amount of suitable habitat in both the present and the future. Including imprecise records also improves estimates of niche breadth and extent of occurrence. An analysis of 44 species of North American Asclepias (Apocynaceae) yielded similar results. Main conclusions Existing studies examining the effects of spatial imprecision typically compare outcomes based on precise records against the same records with spatial error added to them. However, in real‐world cases, analysts possess a mix of precise and imprecise records and must decide whether to retain or discard the latter. Discarding imprecise records can undersample the geographical and environmental distributions of species and lead to mis‐estimation of responses to past and future climate change. Our method, for which we provide a software implementation in the enmSdmX package for R, is simple to use and can help leverage the large number of specimen records that are typically deemed “unusable” because of spatial imprecision in their geolocation.

Exploring metapopulation‐scale suppression alternatives for a global invader in a river network experiencing climate change - Brian D. Healy; Phaedra Budy; Charles. B. Yackulic; Brendan P. Murphy; Robert C. Schelly; Mark C. McKinstry (Conservation Biology, 2023)
Invasive species can dramatically alter ecosystems, but eradication is difficult, and suppression is expensive once they are established. Uncertainties in the potential for expansion and impacts by an invader can lead to delayed and inadequate suppression, allowing for establishment. Metapopulation viability models can aid in planning strategies to improve responses to invaders and lessen invasive species’ impacts, which may be particularly important under climate change. We used a spatially explicit metapopulation viability model to explore suppression strategies for ecologically damaging invasive brown trout ( Salmo trutta ), established in the Colorado River and a tributary in Grand Canyon National Park. Our goals were to estimate the effectiveness of strategies targeting different life stages and subpopulations within a metapopulation; quantify the effectiveness of a rapid response to a new invasion relative to delaying action until establishment; and estimate whether future hydrology and temperature regimes related to climate change and reservoir management affect metapopulation viability and alter the optimal management response. Our models included scenarios targeting different life stages with spatially varying intensities of electrofishing, redd destruction, incentivized angler harvest, piscicides, and a weir. Quasi‐extinction (QE) was obtainable only with metapopulation‐wide suppression targeting multiple life stages. Brown trout population growth rates were most sensitive to changes in age 0 and large adult mortality. The duration of suppression needed to reach QE for a large established subpopulation was 12 years compared with 4 with a rapid response to a new invasion. Isolated subpopulations were vulnerable to suppression; however, connected tributary subpopulations enhanced metapopulation persistence by serving as climate refuges. Water shortages driving changes in reservoir storage and subsequent warming would cause brown trout declines, but metapopulation QE was achieved only through refocusing and increasing suppression. Our modeling approach improves understanding of invasive brown trout metapopulation dynamics, which could lead to more focused and effective invasive species suppression strategies and, ultimately, maintenance of populations of endemic fishes.

A new compositional estimate for refractory lower continental crust with implications for the first terrestrial Pb-isotope paradox - Robert B. Emo; Balz S. Kamber; Hilary Downes; David T. Murphy; John T. Caulfield (Lithos, 2023)

Photochemical model representation of ozone and precursors during the 2017 Lake Michigan ozone study (LMOS) - Kirk R. Baker; Jennifer Liljegren; Lukas Valin; Laura Judd; Jim Szykman; Dylan B. Millet; Alan Czarnetzki; Andrew Whitehill; Ben Murphy; Charles Stanier (Atmospheric Environment, 2023)

Ensuring planetary survival: the centrality of organic carbon in balancing the multifunctional nature of soils - Peter M. Kopittke; Asmeret Asefaw Berhe; Yolima Carrillo; Timothy R. Cavagnaro; Deli Chen; Qing-Lin Chen; Mercedes Román Dobarco; Feike A. Dijkstra; Damien J. Field; Michael J. Grundy; Ji-Zheng He; Frances C. Hoyle; et al. (Critical Reviews in Environmental Science and Technology, 2022)

Links across ecological scales: Plant biomass responses to elevated CO 2 - Julia Maschler; Lalasia Bialic‐Murphy; Joe Wan; Louise C. Andresen; Constantin M. Zohner; Peter B. Reich; Andreas Lüscher; Manuel K. Schneider; Christoph Müller; Gerald Moser; Jeffrey S. Dukes; Inger Kappel Schmidt; et al. (Global Change Biology, 2022)
The degree to which elevated CO 2 concentrations (e[CO 2 ]) increase the amount of carbon (C) assimilated by vegetation plays a key role in climate change. However, due to the short‐term nature of CO 2 enrichment experiments and the lack of reconciliation between different ecological scales, the effect of e[CO 2 ] on plant biomass stocks remains a major uncertainty in future climate projections. Here, we review the effect of e[CO 2 ] on plant biomass across multiple levels of ecological organization, scaling from physiological responses to changes in population‐, community‐, ecosystem‐, and global‐scale dynamics. We find that evidence for a sustained biomass response to e[CO 2 ] varies across ecological scales, leading to diverging conclusions about the responses of individuals, populations, communities, and ecosystems. While the distinct focus of every scale reveals new mechanisms driving biomass accumulation under e[CO 2 ], none of them provides a full picture of all relevant processes. For example, while physiological evidence suggests a possible long‐term basis for increased biomass accumulation under e[CO 2 ] through sustained photosynthetic stimulation, population‐scale evidence indicates that a possible e[CO 2 ]‐induced increase in mortality rates might potentially outweigh the effect of increases in plant growth rates on biomass levels. Evidence at the global scale may indicate that e[CO 2 ] has contributed to increased biomass cover over recent decades, but due to the difficulty to disentangle the effect of e[CO 2 ] from a variety of climatic and land‐use‐related drivers of plant biomass stocks, it remains unclear whether nutrient limitations or other ecological mechanisms operating at finer scales will dampen the e[CO 2 ] effect over time. By exploring these discrepancies, we identify key research gaps in our understanding of the effect of e[CO 2 ] on plant biomass and highlight the need to integrate knowledge across scales of ecological organization so that large‐scale modeling can represent the finer‐scale mechanisms needed to constrain our understanding of future terrestrial C storage.

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Natural and anthropogenic landscape factors shape functional connectivity of an ecological specialist in urban Southern California - Sarah M. Wenner; Melanie A. Murphy; Kathleen S. Delaney; Gregory B. Pauly; Jonathan Q. Richmond; Robert N. Fisher; Jeanne M. Robertson (Molecular Ecology, 2022)
Identifying how natural (i.e., unaltered by human activity) and anthropogenic landscape variables influence contemporary functional connectivity in terrestrial organisms can elucidate the genetic consequences of environmental change. We examine population genetic structure and functional connectivity among populations of a declining species, the Blainville's horned lizard ( Phrynosoma blainvillii ), in the urbanized landscape of the Greater Los Angeles Area in Southern California, USA. Using single nucleotide polymorphism data, we assessed genetic structure among populations occurring at the interface of two abutting evolutionary lineages, and at a fine scale among habitat fragments within the heavily urbanized area. Based on the ecology of P. blainvillii , we predicted which environmental variables influence population structure and gene flow and used gravity models to distinguish among hypotheses to best explain population connectivity. Our results show evidence of admixture between two evolutionary lineages and strong population genetic structure across small habitat fragments. We also show that topography, microclimate, and soil and vegetation types are important predictors of functional connectivity, and that anthropogenic disturbance, including recent fire history and urban development, are key factors impacting contemporary population dynamics. Examining how natural and anthropogenic sources of landscape variation affect contemporary population genetics is critical to understanding how to best manage sensitive species in a rapidly changing landscape.

Effects of modafinil on electroencephalographic microstates in healthy adults - Samantha R. Linton; Michael Murphy; Hans S. Schroder; Micah Breiger; Ann M. Iturra-Mena; Brian D. Kangas; Jack Bergman; William A. Carlezon; Victoria B. Risbrough; Samuel A. Barnes; Andre Der-Avakian; Diego A. Pizzagalli (Psychopharmacology, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Correction to: Lifestyle factors and lung cancer risk among never smokers in the Canadian Partnership for Tomorrow’s Health (CanPath) - Rachel A. Murphy; Maryam Darvishian; Jia Qi; Yixian Chen; Quincy Chu; Jennifer Vena; Trevor J. B. Dummer; Nhu Le; Ellen Sweeney; Vanessa DeClercq; Scott A. Grandy; Melanie R. Keats; et al. (Cancer Causes & Control, 2022)

Lifestyle factors and lung cancer risk among never smokers in the Canadian Partnership for Tomorrow’s Health (CanPath) - Rachel A. Murphy; Maryam Darvishian; Jia Qi; Yixian Chen; Quincy Chu; Jennifer Vena; Trevor J. B. Dummer; Nhu Le; Ellen Sweeney; Vanessa DeClercq; Scott A. Grandy; Melanie R. Keats; et al. (Cancer Causes & Control, 2022)

A decision framework for estimating the cost of marine plastic pollution interventions - Erin L. Murphy; Miranda Bernard; Gwenllian Iacona; Stephanie B. Borrelle; Megan Barnes; Alexis McGivern; Jorge Emmanuel; Leah R. Gerber (Conservation Biology, 2022)
Marine plastic pollution has emerged as one of the most pressing environmental challenges of our time. Although there has been a surge in global investment for implementing interventions to mitigate plastic pollution, there has been little attention given to the cost of these interventions. We developed a decision support framework to identify the economic, social, and ecological costs and benefits of plastic pollution interventions for different sectors and stakeholders. We calculated net cost as a function of six cost and benefit categories with the following equation: cost of implementing an intervention (direct, indirect, and nonmonetary costs) minus recovered costs and benefits (monetary and nonmonetary) produced by the interventions. We applied our framework to two quantitative case studies (a solid waste management plan and a trash interceptor) and four comparative case studies, evaluating the costs of beach cleanups and waste‐to‐energy plants in various contexts, to identify factors that influence the costs of plastic pollution interventions. The socioeconomic context of implementation, the spatial scale of implementation, and the time scale of evaluation all influence costs and the distribution of costs across stakeholders. Our framework provides an approach to estimate and compare the costs of a range of interventions across sociopolitical and economic contexts.

Structure and permeability of the egg capsule of the placental Australian sharpnose shark, Rhizoprionodon taylori - Alice L. Buddle; James U. Van Dyke; Michael B. Thompson; Colin A. Simpfendorfer; Christopher R. Murphy; Margot L. Day; Camilla M. Whittington (Journal of Comparative Physiology B, 2022)
Shark placentae are derived from modifications to the fetal yolk sac and the maternal uterine mucosa. In almost all placental sharks, embryonic development occurs in an egg capsule that remains intact for the entire pregnancy, separating the fetal tissues from the maternal tissues at the placental interface. Here, we investigate the structure and permeability of the egg capsules that surround developing embryos of the placental Australian sharpnose shark ( Rhizoprionodon taylori ) during late pregnancy. The egg capsule is an acellular fibrous structure that is 0.42 ± 0.04 μm thick at the placental interface between the yolk sac and uterine tissues, and 0.67 ± 0.08 μm thick in the paraplacental regions. This is the thinnest egg capsule of any placental shark measured so far, which may increase the diffusion rate of respiratory gases, fetal wastes, water and nutrients between maternal and fetal tissues. Molecules smaller than or equal to ~ 1000 Da can diffuse through the egg capsule, but larger proteins (~ 3000–26,000 Da) cannot. Similar permeability characteristics between the egg capsule of R. taylori and other placental sharks suggest that molecular size is an important determinant of the molecules that can be exchanged between the mother and her embryos during pregnancy.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

The Responsiveness of Gait and Balance Outcomes to Disease Progression in Friedreich Ataxia - Sarah C. Milne; Seok Hun Kim; Anna Murphy; Jane Larkindale; Jennifer Farmer; Ritchie Malapira; Mary Danoudis; Jessica Shaw; Tyagi Ramakrishnan; Fatemeh Rasouli; Eppie M. Yiu; Nellie Georgiou-Karistianis; et al. (The Cerebellum, 2021)

Opportunities and Challenges for Including Oyster-Mediated Denitrification in Nitrogen Management Plans - Julie M. Rose; J. Stephen Gosnell; Suzanne Bricker; Mark J. Brush; Allison Colden; Lora Harris; Eric Karplus; Alix Laferriere; Nathaniel H. Merrill; Tammy B. Murphy; Joshua Reitsma; Johnny Shockley; et al. (Estuaries and Coasts, 2021)
Nitrogen pollution is one of the primary threats to coastal water quality globally, and governmental regulations and marine policy are increasingly requiring nitrogen remediation in management programs. Traditional mitigation strategies (e.g., advanced wastewater treatment) are not always enough to meet reduction goals. Novel opportunities for additional nitrogen reduction are needed to develop a portfolio of long-term solutions. Increasingly, in situ nitrogen reduction practices are providing a complementary management approach to the traditional source control and treatment, including recognition of potential contributions of coastal bivalve shellfish. While policy interest in bivalves has focused primarily on nitrogen removal via biomass harvest, bivalves can also contribute to nitrogen removal by enhancing denitrification (the microbial driven process of bioavailable nitrogen transformation to di-nitrogen gas). Recent evidence suggests that nitrogen removed via enhanced denitrification may eclipse nitrogen removal through biomass harvest alone. With a few exceptions, bivalve-enhanced denitrification has yet to be incorporated into water quality policy. Here, we focus on oysters in considering how this issue may be addressed. We discuss policy options to support expansion of oyster-mediated denitrification, describe the practical considerations for incorporation into nitrogen management, and summarize the current state of the field in accounting for denitrification in oyster habitats. When considered against alternative nitrogen control strategies, we argue that enhanced denitrification associated with oysters should be included in a full suite of nitrogen removal strategies, but with the recognition that denitrification associated with oyster habitats will not alone solve our excess nitrogen loading problem.

Examining the etiology of early-onset breast cancer in the Canadian Partnership for Tomorrow’s Health (CanPath) - Joy Pader; Robert B. Basmadjian; Dylan E. O’Sullivan; Nicole E. Mealey; Yibing Ruan; Christine Friedenreich; Rachel Murphy; Edwin Wang; May Lynn Quan; Darren R. Brenner (Cancer Causes & Control, 2021)

Utilising grassland management and climate data for more accurate prediction of herbage mass using the rising plate meter - D. J. Murphy; P. Shine; B. O’. Brien; M. O’. Donovan; M. D. Murphy (Precision Agriculture, 2021)

Evaluation of the precision of the rising plate meter for measuring compressed sward height on heterogeneous grassland swards - D. J. Murphy; B. O’ Brien; D. Hennessy; M. Hurley; M. D. Murphy (Precision Agriculture, 2021)

A perturbed parameter ensemble of HadGEM3-GC3.05 coupled model projections: part 1: selecting the parameter combinations - David M. H. Sexton; Carol F. McSweeney; John W. Rostron; Kuniko Yamazaki; Ben B. B. Booth; James M. Murphy; Leighton Regayre; Jill S. Johnson; Ambarish V. Karmalkar (Climate Dynamics, 2021)

Argo Data 1999–2019: Two Million Temperature-Salinity Profiles and Subsurface Velocity Observations From a Global Array of Profiling Floats - Annie P. S. Wong; Susan E. Wijffels; Stephen C. Riser; Sylvie Pouliquen; Shigeki Hosoda; Dean Roemmich; John Gilson; Gregory C. Johnson; Kim Martini; David J. Murphy; Megan Scanderbeg; T. V. S. Udaya Bhaskar; et al. (Frontiers in Marine Science, 2020)

Using a Culturally Tailored Narrative to Increase Cervical Cancer Detection Among Spanish-Speaking Mexican-American Women - Carol Y. Ochoa; Sheila T. Murphy; Lauren B. Frank; Lourdes A. Baezconde-Garbanati (Journal of Cancer Education, 2020)

The Convergence of Cell-Based Surface Plasmon Resonance and Biomaterials: The Future of Quantifying Bio-molecular Interactions—A Review - Spencer B. Mamer; Phillip Page; Mary Murphy; Jiaojiao Wang; Pierrick Gallerne; Ali Ansari; P. I. Imoukhuede (Annals of Biomedical Engineering, 2020)

Plastid phylogenomic analysis of tribe Myoporeae (Scrophulariaceae) - Rachael M. Fowler; Todd G. B. McLay; Tanja M. Schuster; Bevan J. Buirchell; Daniel J. Murphy; Michael J. Bayly (Plant Systematics and Evolution, 2020)

A Comparison of the Diagnostic Accuracy of in-situ and Digital Image-Based Assessments of Coral Health and Disease - John H. R. Burns; Grady Weyenberg; Travis Mandel; Sofia B. Ferreira; Drew Gotshalk; Chad K. Kinoshita; Micah J. Marshall; Nicholas A. V. Del Moral; Shane J. Murphy; Kailey H. Pascoe; Alexandra Runyan; Alexander J. Spengler; et al. (Frontiers in Marine Science, 2020)

The potassium channel Kcne3 is a VEGFA-inducible gene selectively expressed by vascular endothelial tip cells - Ron A. Deckelbaum; Ivan B. Lobov; Eunice Cheung; Gabor Halasz; Saathyaki Rajamani; Julia Lerner; Chunxiang Tong; Zhe Li; Patricia Boland; Melissa Dominguez; Virginia Hughes; George D. Yancopoulos; et al. (Angiogenesis, 2020)
Angiogenesis is largely driven by motile endothelial tip-cells capable of invading avascular tissue domains and enabling new vessel formation. Highly responsive to Vascular Endothelial Growth-Factor-A (VEGFA), endothelial tip-cells also suppress angiogenic sprouting in adjacent stalk cells, and thus have been a primary therapeutic focus in addressing neovascular pathologies. Surprisingly, however, there remains a paucity of specific endothelial tip-cell markers. Here, we employ transcriptional profiling and a lacZ reporter allele to identify Kcne3 as an early and selective endothelial tip-cell marker in multiple angiogenic contexts. In development, Kcne3 expression initiates during early phases of angiogenesis (E9) and remains specific to endothelial tip-cells, often adjacent to regions expressing VEGFA. Consistently, Kcne3 activation is highly responsive to exogenous VEGFA but maintains tip-cell specificity throughout normal retinal angiogenesis. We also demonstrate endothelial tip-cell selectivity of Kcne3 in several injury and tumor models. Together, our data show that Kcne3 is a unique marker of sprouting angiogenic tip-cells and offers new opportunities for investigating and targeting this cell type.

Development of a nanomedicine-loaded hydrogel for sustained delivery of an angiogenic growth factor to the ischaemic myocardium - Joanne O’Dwyer; Robert Murphy; Eimear B. Dolan; Lenka Kovarova; Martin Pravda; Vladimir Velebny; Andreas Heise; Garry P. Duffy; Sally Ann Cryan (Drug Delivery and Translational Research, 2020)

Using emerging hot spot analysis of stranding records to inform conservation management of a data-poor cetacean species - Emma L. Betty; Barbara Bollard; Sinéad Murphy; Mike Ogle; Hannah Hendriks; Mark B. Orams; Karen A. Stockin (Biodiversity and Conservation, 2020)

Toward the Integrated Marine Debris Observing System - Nikolai Maximenko; Paolo Corradi; Kara Lavender Law; Erik Van Sebille; Shungudzemwoyo P. Garaba; Richard Stephen Lampitt; Francois Galgani; Victor Martinez-Vicente; Lonneke Goddijn-Murphy; Joana Mira Veiga; Richard C. Thompson; Christophe Maes; et al. (Frontiers in Marine Science, 2019)

Finding plausible and diverse variants of a climate model. Part II: development and validation of methodology - Ambarish V. Karmalkar; David M. H. Sexton; James M. Murphy; Ben B. B. Booth; John W. Rostron; Doug J. McNeall (Climate Dynamics, 2019)

Finding plausible and diverse variants of a climate model. Part 1: establishing the relationship between errors at weather and climate time scales - D. M. H. Sexton; A. V. Karmalkar; J. M. Murphy; K. D. Williams; I. A. Boutle; C. J. Morcrette; A. J. Stirling; S. B. Vosper (Climate Dynamics, 2019)

See how they run: increased ranging behavior counters potential Allee effects in experimentally introduced house mice on an island - J. W. B. MacKay; J. C. Russell; M. N. Clout; E. C. Murphy; M. E. Hauber (Biological Invasions, 2019)

Training population selection and use of fixed effects to optimize genomic predictions in a historical USA winter wheat panel - J. Martin Sarinelli; J. Paul Murphy; Priyanka Tyagi; James B. Holland; Jerry W. Johnson; Mohamed Mergoum; Richard E. Mason; Ali Babar; Stephen Harrison; Russell Sutton; Carl A. Griffey; Gina Brown-Guedira (Theoretical and Applied Genetics, 2019)

El Niño–Southern Oscillation incidence over long dry sequences and their impact on soil water storage in Argentina - Olga C. Penalba; Vanesa C. Pántano; Liliana B. Spescha; Guillermo M. Murphy (International Journal of Climatology, 2019)
The deficit of daily precipitation, persistent over time (long dry sequences [LDS]), causes economic losses in the east–northeast of Argentina where agriculture production is the main economic activity. For this reason, an improvement in the seasonal prediction of the frequency of precipitation is required. Among several forcings influencing the region of study, El Niño–Southern Oscillation (ENSO) has been identified as responsible for a great part of the inter‐annual variability of precipitation. Therefore, in this study, we assess the ENSO signal on LDS and the response of soil water storage under the different phases. In order to assess this issue, daily data were used from 30 meteorological stations. Based on this information, dry sequences were quantified considering a dry day when the accumulated precipitation of two consecutive days was lower than 5 mm. From the dry sequences, two different thresholds were used to identify LDS. On one hand, the 85th percentile was selected as a spatially variable threshold and, on the other hand, 15‐day length was used as a fixed one. Based on this selection, the severity and the number of LDS were analysed. In general terms, La Niña (El Niño) phase presents higher (lower) severity and higher (lower) probability in the occurrence of more than one LDS per season, except in winter. This result is in concordance with negative (positive) anomalies of accumulated precipitation under La Niña (El Niño) phase. Regarding the impact on the water balance, soil water storage responds to accumulated precipitation anomalies in all the seasons.

Iclaprim activity against wild-type and corresponding thymidine kinase–deficient Staphylococcus aureus in a mouse protection model - David B. Huang; Jee Hyun Park; Timothy M. Murphy (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

An injectable alginate/extra cellular matrix (ECM) hydrogel towards acellular treatment of heart failure - Clive J. Curley; Eimear B. Dolan; Matthias Otten; Svenja Hinderer; Garry P. Duffy; Bruce P. Murphy (Drug Delivery and Translational Research, 2019)

Physiologic serum 1,25 dihydroxyvitamin D is inversely associated with prostatic Ki67 staining in a diverse sample of radical prostatectomy patients - Adrian Rosenberg; Oluwarotimi S. Nettey; Pooja Gogana; Ujalla Sheikh; Virgilia Macias; Andre Kajdacsy-Balla; Roohollah Sharifi; Rick A. Kittles; Adam B. Murphy (Cancer Causes & Control, 2019)

Impact of toll-like receptor 4 stimulation on human neonatal neutrophil spontaneous migration, transcriptomics, and cytokine production - Steven L. Raymond; Russell B. Hawkins; Tyler J. Murphy; Jaimar C. Rincon; Julie A. Stortz; María Cecilia López; Ricardo Ungaro; Felix Ellett; Henry V. Baker; James L. Wynn; Lyle L. Moldawer; Daniel Irimia; et al. (Journal of Molecular Medicine, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Correction to: Arctic Micromonas uses protein pools and non-photochemical quenching to cope with temperature restrictions on Photosystem II protein turnover - Guangyan Ni; Gabrielle Zimbalatti; Cole D. Murphy; Audrey B. Barnett; Christopher M. Arsenault; Gang Li; Amanda M. Cockshutt; Douglas A. Campbell (Photosynthesis Research, 2018)

Efficacy evaluation of iclaprim in a neutropenic rat lung infection model with methicillin-resistant Staphylococcus aureus entrapped in alginate microspheres - David B. Huang; Ian Morrissey; Timothy Murphy; Stephen Hawser; Mark H. Wilcox (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Effects of Gestation Pens Versus Stalls and Wet Versus Dry Feed on Air Contaminants in Swine Production - Peter C. Raynor; Shannon Engelman; Darby Murphy; Gurumurthy Ramachandran; Jeffrey B. Bender; Bruce H. Alexander (Journal of Agromedicine, 2018)

Glucuronide and Sulfate Conjugates of Bisphenol A: Chemical Synthesis and Correlation Between Their Urinary Levels and Plasma Bisphenol A Content in Voluntary Human Donors - Ka-Lok Ho; Ka-Ki Yuen; Man-Shan Yau; Margaret B. Murphy; Yi Wan; Bonnie M.-W. Fong; Sidney Tam; John P. Giesy; Kelvin S.-Y. Leung; Michael H.-W. Lam (Archives of Environmental Contamination and Toxicology, 2017)

Assessing how accumulated precipitation and long dry sequences impact the soil water storage - Vanesa C. Pántano; Olga C. Penalba; Liliana B. Spescha; Guillermo M. Murphy (International Journal of Climatology, 2017)
Precipitation or no precipitation persistent over time often became extreme weather conditions with greater regional economic impact. The temporal and spatial variability of these variables, together with the evapotranspiration, is crucial in the east‐northeast of Argentina, where rain‐fed agricultural production is carried out. In this work, the frequency of precipitation was studied from dry spells and complemented with an analysis of the accumulated precipitation and evapotranspiration. In particular, dry sequences longer than 15 days, return period and severity, were the focus of this study. Finally, the impact of the amount and frequency of precipitation on soil water storage was assessed through a decadal analysis. The region of study is characterized by northeast‐southwest gradient in accumulated precipitation and east–west gradient in winter long dry sequences. During summer, higher and more frequent precipitations (lower probability of long dry sequences and lower return period of 15 days and severity) were presented whereas the opposite was found in winter. However, the stations located to the west presented the highest probability of long dry sequences with higher severity and lower accumulated precipitation. This result highlights the vulnerability of the agriculture activity in the western stations. Regarding the impact of long dry sequences over soil water storage, the seasonality of evapotranspiration is also involved. The impact is stronger during austral summer because of higher values of evapotranspiration and it is lower during winter, in spite of the higher probability of long sequences. Decadal analysis suggested that soil water storage responds to precipitation amount or frequency depending on the magnitude of the anomalies. In this sense, the impact of precipitation over soil water storage depends on how it is distributed.

Gene expression profiles predictive of cold-induced sweetening in potato - Jonathan Neilson; M. Lagüe; S. Thomson; F. Aurousseau; A. M. Murphy; B. Bizimungu; V. Deveaux; Y. Bègue; J. M. E. Jacobs; H. H. Tai (Functional & Integrative Genomics, 2017)

New approaches to antibiotic discovery - C. Kealey; C. A. Creaven; C. D. Murphy; C. B. Brady (Biotechnology Letters, 2017)

Arctic Micromonas uses protein pools and non-photochemical quenching to cope with temperature restrictions on Photosystem II protein turnover - Guangyan Ni; Gabrielle Zimbalatti; Cole D. Murphy; Audrey B. Barnett; Christopher M. Arsenault; Gang Li; Amanda M. Cockshutt; Douglas A. Campbell (Photosynthesis Research, 2017)

Expression of VEGF 111 and other VEGF-A variants in the rat uterus is correlated with stage of pregnancy - Camilla M. Whittington; Kevin Danastas; Georges E. Grau; Christopher R. Murphy; Michael B. Thompson (Journal of Comparative Physiology B, 2017)

Profiling of Selected Functional Metabolites in the Central Nervous System of Marine Medaka (Oryzias melastigma) for Environmental Neurotoxicological Assessments - Elva Ngai-Yu Lei; Man-Shan Yau; Chi-Chung Yeung; Margaret B. Murphy; Ka-Leung Wong; Michael Hon-Wah Lam (Archives of Environmental Contamination and Toxicology, 2017)

Oxygen tension modulates the effects of TNFα in compressed chondrocytes - R. K. Tilwani; S. Vessillier; B. Pingguan-Murphy; D. A. Lee; D. L. Bader; T. T. Chowdhury (Inflammation Research, 2017)

Comparison of abdominal adiposity and overall obesity in relation to risk of small intestinal cancer in a European Prospective Cohort - Yunxia Lu; Amanda J. Cross; Neil Murphy; Heinz Freisling; Ruth C. Travis; Pietro Ferrari; Verena A. Katzke; Rudolf Kaaks; Åsa Olsson; Ingegerd Johansson; Frida Renström; Salvatore Panico; et al. (Cancer Causes & Control, 2016)

Effects of 4-methylbenzylidene camphor (4-MBC) on neuronal and muscular development in zebrafish (Danio rerio) embryos - Vincent Wai Tsun Li; Mei Po Mirabelle Tsui; Xueping Chen; Michelle Nga Yu Hui; Ling Jin; Raymond H. W. Lam; Richard Man Kit Yu; Margaret B. Murphy; Jinping Cheng; Paul Kwan Sing Lam; Shuk Han Cheng (Environmental Science and Pollution Research, 2016)

Determinants of the t(14;18) translocation and their role in t(14;18)-positive follicular lymphoma - Rachel S. Kelly; Sandrine Roulland; Ester Morgado; Stéphanie Sungalee; Nathalie Jouve; Rosario Tumino; Vittorio Krogh; Salvatore Panico; Silvia Polidoro; Giovanna Masala; María-José Sánchez; Maria-Dolores Chirlaque; et al. (Cancer Causes & Control, 2015)

Desert spring refugia: museums of diversity or evolutionary cradles? - Nicholas P. Murphy; Michelle T. Guzik; Steven J. B. Cooper; Andrew D. Austin (Zoologica Scripta, 2015)
Refugia play a critical role in preserving species unable to move or adapt to cope with environmental change. The role of refugia as ‘museums of diversity’ means these environments have a high conservation priority. Less well known, however, is the role that isolated and fragmented refugia can play in the generation of new diversity. Here, we examined the diversification and evolutionary history of a community of endemic invertebrates that inhabit Australian desert spring refugia. We compared the phylogenies of seven endemic groups ( Haloniscus and Phreatomerus isopods, chiltoniid amphipods, Ngarawa ostracods, Trochidrobia and Fonscochlea snails and Gymnochthebius beetles) from these springs and examine the rates and timing of diversification and reconstructed the phylogeographic history of each taxon. Despite major life‐history differences among these taxa, they demonstrate remarkable similarities in their evolutionary histories. All groups have multiple lineages that extend back to a time before the formation of present‐day deserts, and significant geographic‐based diversification since adapting to a refugial habitat. The results provide further evidence that refugia act as museums of biodiversity, preserving lineages that would have otherwise gone extinct. However, we also observed that isolation in refugia corresponds with significant diversification, leading to a recently evolved, novel endemic fauna, supporting the idea that fragmented refugia provide ideal conditions for the generation of future biodiversity hotspots.

Engineered Fibrin Gels for Parallel Stimulation of Mesenchymal Stem Cell Proangiogenic and Osteogenic Potential - Kaitlin C. Murphy; Marissa L. Hughbanks; Bernard Y. K. Binder; Caroline B. Vissers; J. Kent Leach (Annals of Biomedical Engineering, 2015)

Evaluating the landscape of fear between apex predatory sharks and mobile sea turtles across a large dynamic seascape - Neil Hammerschlag; Annette C. Broderick; John W. Coker; Michael S. Coyne; Mark Dodd; Michael G. Frick; Matthew H. Godfrey; Brendan J. Godley; DuBose B. Griffin; Kyra Hartog; Sally R. Murphy; Thomas M. Murphy; et al. (Ecology, 2015)
The “landscape of fear” model has been proposed as a unifying concept in ecology, describing, in part, how animals behave and move about in their environment. The basic model predicts that as an animal's landscape changes from low to high risk of predation, prey species will alter their behavior to risk avoidance. However, studies investigating and evaluating the landscape of fear model across large spatial scales (tens to hundreds of thousands of square kilometers) in dynamic, open, aquatic systems involving apex predators and highly mobile prey are lacking. To address this knowledge gap, we investigated predator–prey relationships between tiger sharks ( Galeocerdo cuvier ) and loggerhead turtles ( Caretta caretta ) in the North Atlantic Ocean. This included the use of satellite tracking to examine shark and turtle distributions as well as their surfacing behaviors under varying levels of home range overlap. Our findings revealed patterns that deviated from our a priori predictions based on the landscape of fear model. Specifically, turtles did not alter their surfacing behaviors to risk avoidance when overlap in shark–turtle core home range was high. However, in areas of high overlap with turtles, sharks exhibited modified surfacing behaviors that may enhance predation opportunity. We suggest that turtles may be an important factor in determining shark distribution, whereas for turtles, other life history trade‐offs may play a larger role in defining their habitat use. We propose that these findings are a result of both biotic and physically driven factors that independently or synergistically affect predator–prey interactions in this system. These results have implications for evolutionary biology, community ecology, and wildlife conservation. Further, given the difficulty in studying highly migratory marine species, our approach and conclusions may be applied to the study of other predator–prey systems.

Improving estimates of tropical peatland area, carbon storage, and greenhouse gas fluxes - I. T. Lawson; T. J. Kelly; P. Aplin; A. Boom; G. Dargie; F. C. H. Draper; P. N. Z. B. P. Hassan; J. Hoyos-Santillan; J. Kaduk; D. Large; W. Murphy; S. E. Page; et al. (Wetlands Ecology and Management, 2015)

Sensitivity of Spatiotemporal Gait Parameters in Measuring Disease Severity in Friedreich Ataxia - Sarah C. Milne; Darren R. Hocking; Nellie Georgiou-Karistianis; Anna Murphy; Martin B. Delatycki; Louise A. Corben (The Cerebellum, 2014)

Common vitamin D pathway gene variants reveal contrasting effects on serum vitamin D levels in African Americans and European Americans - Ken Batai; Adam B. Murphy; Ebony Shah; Maria Ruden; Jennifer Newsome; Sara Agate; Michael A. Dixon; Hua Yun Chen; Leslie A. Deane; Courtney M. P. Hollowell; Chiledum Ahaghotu; Rick A. Kittles (Human Genetics, 2014)

Transient climate changes in a perturbed parameter ensemble of emissions-driven earth system model simulations - James M. Murphy; Ben B. B. Booth; Chris A. Boulton; Robin T. Clark; Glen R. Harris; Jason A. Lowe; David M. H. Sexton (Climate Dynamics, 2014)

Assessment of the CMIP5 global climate model simulations of the western tropical Pacific climate system and comparison to CMIP3 - Michael R. Grose; Jaclyn N. Brown; Sugata Narsey; Josephine R. Brown; Bradley F. Murphy; Clothilde Langlais; Alex Sen Gupta; Aurel F. Moise; Damien B. Irving (International Journal of Climatology, 2014)
A set of 27 global climate models from the Coupled Model Inter‐comparison Project Phase 5 ( CMIP5 ) ensemble are assessed for their performance for the purpose of making future climate projection studies in the western tropical Pacific and differences to Coupled Model Inter‐comparison Project Phase 3 ( CMIP3 ) are assessed. The CMIP5 models show some improvements upon CMIP3 in the simulation of the climate in the western tropical Pacific in the late 20th century. There are fewer CMIP5 models with very poor skill scores than in CMIP3 for some measures and a small group of the well‐performing models in CMIP5 have lower biases than in an equivalent group from CMIP3 . These best‐performing models could be particularly informative for studying certain climate sensitivities and feedbacks in the region. There is evidence to reject one model as unsuitable for making regional climate projections in the region, and another two models unsuitable for analysis of the South Pacific Convergence Zone (SPCZ). However, while there have been improvements, many of the systematic model biases in the mean climate in CMIP3 are also present in the CMIP5 models. They are primarily related to the shape of the transition between the Indo‐Pacific warm pool and equatorial cold tongue, and the associated biases in the position and orientation of the SPCZ and Inter‐Tropical Convergence Zone, as well as in the spatial pattern, variability and teleconnections of the West Pacific monsoon, and the simulation of El Niño Southern Oscillation. Overall, the results show that careful interpretation and consideration of biases is required when using CMIP5 outputs for generating regional climate projections for the western tropical Pacific, particularly at the country scale, just as there was with CMIP3 .

3D ground model development for an active landslide in Lias mudrocks using geophysical, remote sensing and geotechnical methods - A. J. Merritt; J. E. Chambers; W. Murphy; P. B. Wilkinson; L. J. West; D. A. Gunn; P. I. Meldrum; M. Kirkham; N. Dixon (Landslides, 2014)

The Ediacaran–Early Cambrian detrital zircon record of NW Iberia: possible sources and paleogeographic constraints - J. Fernández-Suárez; G. Gutiérrez-Alonso; D. Pastor-Galán; M. Hofmann; J. B. Murphy; U. Linnemann (International Journal of Earth Sciences, 2014)

Spatial and Temporal Assessment of Cumulative Disturbance Impacts Due to Military Training, Burning, Haying, and Their Interactions on Land Condition of Fort Riley - Guangxing Wang; Dana Murphy; Adam Oller; Heidi R. Howard; Alan B. Anderson; Santosh Rijal; Natalie R. Myers; Philip Woodford (Environmental Management, 2014)

Modulation of Mcl-1 sensitizes glioblastoma to TRAIL-induced apoptosis - Á. C. Murphy; B. Weyhenmeyer; J. Noonan; S. M. Kilbride; S. Schimansky; K. P. Loh; D. Kögel; A. G. Letai; J. H. M. Prehn; B. M. Murphy (Apoptosis, 2014)

Cancer risk and genotype–phenotype correlations in PTEN hamartoma tumor syndrome - Marry H. Nieuwenhuis; C. Marleen Kets; Maureen Murphy-Ryan; Helger G. Yntema; D. Gareth Evans; Chrystelle Colas; Pal Møller; Frederik J. Hes; Shirley V. Hodgson; Maran J. W. Olderode-Berends; Stefan Aretz; Karl Heinimann; et al. (Familial Cancer, 2014)

Foraging habitats and migration corridors utilized by a recovering subpopulation of adult female loggerhead sea turtles: implications for conservation - DuBose B. Griffin; Sally R. Murphy; Michael G. Frick; Annette C. Broderick; John W. Coker; Michael S. Coyne; Mark G. Dodd; Matthew H. Godfrey; Brendan J. Godley; Lucy A. Hawkes; Thomas M. Murphy; Kristina L. Williams; et al. (Marine Biology, 2013)

Selective changes in cerebellar-cortical processing following motor training - H. Haavik; B. A. Murphy (Experimental Brain Research, 2013)

Interactions between perturbations to different Earth system components simulated by a fully-coupled climate model - F. Hugo Lambert; Glen R. Harris; Matthew Collins; James M. Murphy; David M. H. Sexton; Ben B. B. Booth (Climate Dynamics, 2013)

Decreased consumption of sweet fluids in mu opioid receptor knockout mice: a microstructural analysis of licking behavior - Sean B. Ostlund; Alisa Kosheleff; Nigel T. Maidment; Niall P. Murphy (Psychopharmacology, 2013)

Dark Carbon Fixation in the Columbia River’s Estuarine Turbidity Maxima: Molecular Characterization of Red-Type cbbL Genes and Measurement of DIC Uptake Rates in Response to Added Electron Donors - S. L. Bräuer; K. Kranzler; N. Goodson; D. Murphy; H. M. Simon; A. M. Baptista; B. M. Tebo (Estuaries and Coasts, 2013)

Probabilistic projections of transient climate change - Glen R. Harris; David M. H. Sexton; Ben B. B. Booth; Mat Collins; James M. Murphy (Climate Dynamics, 2013)

Large-scale rodent control reduces pre- and post-dispersal seed predation of the endangered Hawaiian lobeliad, Cyanea superba subsp. superba (Campanulaceae) - Richard J. Pender; Aaron B. Shiels; Lalasia Bialic-Murphy; Stephen M. Mosher (Biological Invasions, 2013)

Current evidence for human yersiniosis in Ireland - T. Ringwood; B. P. Murphy; N. Drummond; J. F. Buckley; A. P. Coveney; H. P. Redmond; J. P. Power; S. Fanning; M. B. Prentice (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Erratum to: Progression of cutaneous melanoma: implications for treatment - Stanley P. L. Leong; Martin C. Mihm; George F. Murphy; Dave S. B. Hoon; Mohammed Kashani-Sabet; Sanjiv S. Agarwala; Jonathan S. Zager; Axel Hauschild; Vernon K. Sondak; Valerie Guild; John M. Kirkwood (Clinical & Experimental Metastasis, 2012)

Progression of cutaneous melanoma: implications for treatment - Stanley P. L. Leong; Martin C. Mihm; George F. Murphy; Dave S. B. Hoon; Mohammed Kashani-Sabet; Sanjiv S. Agarwala; Jonathan S. Zager; Axel Hauschild; Vernon K. Sondak; Valerie Guild; John M. Kirkwood (Clinical & Experimental Metastasis, 2012)

Variation in Cell Wall Composition and Accessibility in Relation to Biofuel Potential of Short Rotation Coppice Willows - Michael J. Ray; Nicholas J. B. Brereton; Ian Shield; Angela Karp; Richard J. Murphy (BioEnergy Research, 2012)

Trapped in desert springs: phylogeography of Australian desert spring snails - Nicholas P. Murphy; Martin F. Breed; Michelle T. Guzik; Steven J. B. Cooper; Andrew D. Austin (Journal of Biogeography, 2012)
Aim We investigate the phylogeographical history and determine the time‐scale of population divergence of hydrobiid freshwater snails (genus Trochidrobia ) inhabiting groundwater springs in the Australian desert. We test the hypothesis that divergence between geographically distinct snail populations occurred simultaneously due to their isolation in hydrologically discrete spring systems, i.e. ‘trapped in desert springs’. Location Groundwater springs of the Great Artesian Basin (GAB) in central Australia. Methods DNA sequence data from the mitochondrial cytochrome c oxidase subunit I gene and the nuclear 28S and internal transcribed spacer rRNA genes were used to reconstruct phylogenetic relationships within and among three species of Trochidrobia (Hydrobiidae): T. punicea (13 spring groups, n = 90) , T. smithi (12 spring groups, n = 62) and T. minuta (2 spring groups, n = 4). Bayesian relaxed molecular clock analyses and approximate Bayesian computation were used to date lineage divergence and distinguish between alternative biogeographical scenarios. Results The diversification of the three Trochidrobia species probably occurred between 2.54 and 9.3 Ma, prior to the formation of the springs c . 1 Ma. Intraspecific divergences within the two widespread species occurred after the formation and colonization of the springs. Coalescent modelling and molecular clock analyses supported a simultaneous radiation of five allopatric intraspecific snail lineages within T. punicea (two lineages) and T. smithi (three lineages) across the GAB springs examined. Main conclusions The analyses support the ‘trapped in desert springs’ hypothesis for the diversification of intraspecific lineages within the species T. punicea and T. smithi . This hypothesis suggests that the formation of deserts around Lake Eyre in the early Pleistocene led to the hydrological isolation of spring complexes in the GAB, resulting in significant molecular divergence, but no morphological divergence, of Trochidrobia snail populations.

Within-season dynamics of red palm mite (Raoiella indica) and phytoseiid predators on two host palm species in south-west India - B. Taylor; P. M. Rahman; S. T. Murphy; V. V. Sudheendrakumar (Experimental and Applied Acarology, 2012)

Decreased soil microbial biomass and nitrogen mineralisation with Eucalyptus biochar addition to a coarse textured soil - D. N. Dempster; D. B. Gleeson; Z. M. Solaiman; D. L. Jones; D. V. Murphy (Plant and Soil, 2012)

Occurrence of glyphosate and acidic herbicides in select urban rivers and streams in Canada, 2007 - Nancy E. Glozier; John Struger; Allan J. Cessna; Melissa Gledhill; Myriam Rondeau; William R. Ernst; Mark A. Sekela; Steve J. Cagampan; Ed Sverko; Clair Murphy; Janine L. Murray; David B. Donald (Environmental Science and Pollution Research, 2012)

CETP polymorphisms associate with brain structure, atrophy rate, and Alzheimer’s disease risk in an APOE-dependent manner - Elizabeth A. Murphy; John Cooper Roddey; Linda K. McEvoy; Dominic Holland; D. J. Hagler; Anders M. Dale; James B. Brewer (Brain Imaging and Behavior, 2012)

Changes in aquatic macrophyte communities in Loch Leven: evidence of recovery from eutrophication? - B. Dudley; I. D. M. Gunn; L. Carvalho; I. Proctor; M. T. O’Hare; K. J. Murphy; A. Milligan (Hydrobiologia, 2012)

Impulsive behaviour induced by both NMDA receptor antagonism and GABAA receptor activation in rat ventromedial prefrontal cortex - Emily R. Murphy; Anushka B. P. Fernando; Gonzalo P. Urcelay; Emma S. J. Robinson; Adam C. Mar; David E. H. Theobald; Jeffrey W. Dalley; Trevor W. Robbins (Psychopharmacology, 2012)

Complex geometry of the Cenozoic magma plumbing system in the central Sahara, NW Africa - J. Duncan Keppie; J. Dostal; J. B. Murphy (International Geology Review, 2011)

Mineral system analysis of the Mt Isa–McArthur River region, Northern Australia - F. C. Murphy; L. J. Hutton; J. L. Walshe; J. S. Cleverley; M. A. Kendrick; J. Mclellan; M. J. Rubenach; N.H. S. Oliver; K. Gessner; F. P. Bierlein; B. Jupp; L. Aillères; et al. (Australian Journal of Earth Sciences, 2011)

Vascular endothelium-specific overexpression of human catalase in cloned pigs - J. J. Whyte; M. Samuel; E. Mahan; J. Padilla; G. H. Simmons; A. A. Arce-Esquivel; S. B. Bender; K. M. Whitworth; Y. H. Hao; C. N. Murphy; E. M. Walters; R. S. Prather; et al. (Transgenic Research, 2011)

A multinational study of neurological performance in antiretroviral therapy-naïve HIV-1-infected persons in diverse resource-constrained settings - Kevin Robertson; Johnstone Kumwenda; Khuanchai Supparatpinyo; Jeanne H. Jiang; Scott Evans; Thomas B. Campbell; Richard W. Price; Robert Murphy; Colin Hall; Christina M. Marra; Cheryl Marcus; Baiba Berzins; et al. (Journal of NeuroVirology, 2011)

A review of the evolution of viviparity in squamate reptiles: the past, present and future role of molecular biology and genomics - Bridget F. Murphy; Michael B. Thompson (Journal of Comparative Physiology B, 2011)

Are the eucalypt and non-eucalypt components of Australian tropical savannas independent? - M. J. Lawes; B. P. Murphy; J. J. Midgley; J. Russell-Smith (Oecologia, 2011)

Climate model errors, feedbacks and forcings: a comparison of perturbed physics and multi-model ensembles - Matthew Collins; Ben B. B. Booth; B. Bhaskaran; Glen R. Harris; James M. Murphy; David M. H. Sexton; Mark J. Webb (Climate Dynamics, 2011)

Genetic structure of the southeastern United States loggerhead turtle nesting aggregation: evidence of additional structure within the peninsular Florida recovery unit - Brian M. Shamblin; Mark G. Dodd; Dean A. Bagley; Llewellyn M. Ehrhart; Anton D. Tucker; Chris Johnson; Raymond R. Carthy; Russell A. Scarpino; Erin McMichael; David S. Addison; Kristina L. Williams; Michael G. Frick; et al. (Marine Biology, 2011)

Culturable Rhodobacter and Shewanella species are abundant in estuarine turbidity maxima of the Columbia River - S. L. Bräuer; C. Adams; K. Kranzler; D. Murphy; M. Xu; P. Zuber; H. M. Simon; A. M. Baptista; B. M. Tebo (Environmental Microbiology, 2011)
Summary Measurements of dissolved, ascorbate‐reducible and total Mn by ICP‐OES revealed significantly higher concentrations during estuarine turbidity maxima (ETM) events, compared with non‐events in the Columbia River. Most probable number (MPN) counts of Mn‐oxidizing or Mn‐reducing heterotrophs were not statistically different from that of other heterotrophs (10 3 –10 4 cells ml −1 ) when grown in defined media, but counts of Mn oxidizers were significantly lower in nutrient‐rich medium (13 cells ml −1 ). MPN counts of Mn oxidizers were also significantly lower on Mn(III)‐pyrophosphate and glycerol (21 cells ml −1 ). Large numbers of Rhodobacter spp. were cultured from dilutions of 10 −2 to 10 −5 , and many of these were capable of Mn(III) oxidation. Up to c . 30% of the colonies tested LBB positive, and all 77 of the successfully sequenced LBB positive colonies (of varying morphology) yielded sequences related to Rhodobacter spp. qPCR indicated that a cluster of Rhodobacter isolates and closely related strains (95–99% identity) represented approximately 1–3% of the total Bacteria , consistent with clone library results. Copy numbers of SSU rRNA genes for either Rhodobacter spp. or Bacteria were four to eightfold greater during ETM events compared with non‐events. Strains of a Shewanella sp. were retrieved from the highest dilutions (10 −5 ) of Mn reducers, and were also capable of Mn oxidation. The SSU rRNA gene sequences from these strains shared a high identity score (98%) with sequences obtained in clone libraries. Our results support previous findings that ETMs are zones with high microbial activity. Results indicated that Shewanella and Rhodobacter species were present in environmentally relevant concentrations, and further demonstrated that a large proportion of culturable bacteria, including Shewanella and Rhodobacter spp., were capable of Mn cycling in vitro .

A Numerical Methodology to Fully Elucidate the Altered Wall Shear Stress in a Stented Coronary Artery - Jonathan B. Murphy; Fergal J. Boyle (Cardiovascular Engineering and Technology, 2010)

QTL Mapping of Enzymatic Saccharification in Short Rotation Coppice Willow and Its Independence from Biomass Yield - Nicholas J. B. Brereton; Frederic E. Pitre; Steven J. Hanley; Michael J. Ray; Angela Karp; Richard J. Murphy (BioEnergy Research, 2010)

The effects of feeding history and environment on condition, body composition and growth of bluegills Lepomis macrochirus - T. Copeland; B. R. Murphy; J. J. Ney (Journal of Fish Biology, 2010)
Initial relative mass ( W R , low v . high) and energetic trajectory in time (starved v . fed) were experimentally manipulated in bluegill Lepomis macrochirus . Fed fish starting at low W R grew more and gained more W R than fed fish starting at high W R . Similarly, starved fish starting at high W R lost more mass and W R than did starved fish starting at low W R . Temporal changes in other variables did not consistently match that of W R , but, by the end of the experiment, proximate composition showed a high correlation to W R . Regression slopes of W R on proximate composition increased with time in the laboratory. Differences between wild and laboratory fish appeared to result from relaxation of environmental stress. When excess resources are available such that L. macrochirus grow, condition indices will increase, but individual response will depend on initial values and thus past environmental experience.

Diabetes mellitus and apoptosis: inflammatory cells - Aidan Ryan; Madeline Murphy; Catherine Godson; Fionnuala B. Hickey (Apoptosis, 2009)

Projecting Cumulative Benefits of Multiple River Restoration Projects: An Example from the Sacramento-San Joaquin River System in California - G. Mathias Kondolf; Paul L. Angermeier; Kenneth Cummins; Thomas Dunne; Michael Healey; Wim Kimmerer; Peter B. Moyle; Dennis Murphy; Duncan Patten; Steve Railsback; Denise J. Reed; Robert Spies; et al. (Environmental Management, 2008)

Folate and MTHFR: risk of adenoma recurrence in the Polyp Prevention Trial - Gwen Murphy; Leah B. Sansbury; Amanda J. Cross; Rachael Stolzenberg-Solomon; Adeyinka Laiyemo; Paul S. Albert; Zhuoqiao Wang; Arthur Schatzkin; Teresa Lehman; Aravind Kalidindi; Rama Modali; Elaine Lanza (Cancer Causes & Control, 2008)

Predicting dispersal and recruitment of Miconia calvescens (Melastomataceae) in Australian tropical rainforests - Helen T. Murphy; B. D. Hardesty; C. S. Fletcher; D. J. Metcalfe; D. A. Westcott; S. J. Brooks (Biological Invasions, 2008)

Modulation of steroidogenesis by coastal waters and sewage effluents of Hong Kong, China, using the H295R assay - Tannia Gracia; Paul D. Jones; Eric B. Higley; Klara Hilscherova; John L. Newsted; Margaret B. Murphy; Alice K. Y. Chan; Xiaowei Zhang; Markus Hecker; Paul K. S. Lam; Rudolf S. S. Wu; John P. Giesy (Environmental Science and Pollution Research, 2008)

Nitrogen Use Efficiency Characteristics of Andigena and Diploid Potato Selections - B. J. Zebarth; T. R. Tarn; H. de Jong; A. Murphy (American Journal of Potato Research, 2008)

The tight junctional protein occludin is found in the uterine epithelium of squamate reptiles - Joanna M. Biazik; Michael B. Thompson; Christopher R. Murphy (Journal of Comparative Physiology B, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Larval development of the Ambon damselfish Pomacentrus amboinensis , with a summary of pomacentrid development - B. F. Murphy; J. M. Leis; K. D. Kavanagh (Journal of Fish Biology, 2007)
Morphological development of the larvae of the Ambon damselfish Pomacentrus amboinensis from the Great Barrier Reef, Australia, is described from 34 reared specimens (2·5–13·0 mm standard length), and two wild settlement‐stage larvae (10·8–11·3 mm) captured in light traps. Reared larvae emerged from demersal eggs at c . 2·5 mm, underwent notochord flexion at 4·0–4·5 mm, and settled at 11–13 mm at 19–21 days after hatching (within the known range for wild larvae). Reared larvae grew at 0·3 mm day −1 (preflexion) to 0·5 mm day −1 (postflexion). Development was direct with few specializations for pelagic existence and was typical of pomacentrids. Head spination consisted of very weak spines on the preopercle, opercle, interopercle, subopercle and supracleithrum. Development of the olfactory system and retina are also described. A summary of published descriptions of early life‐history stages of pomacentrid damselfishes is provided ( n = 15% of known species). Larvae of several genera ( e.g. Abudefduf , Chromis and Stegastes ) are deeper‐bodied and more ‘hunchbacked’ than P. amboinensis . Larvae of other genera ( e.g. Amblyglyphidodon, Chrysiptera and Neoglyphidodon ) are similar to P. amboinensis . Larvae of only three other Pomacentrus species have been described, and they are similar to P. amboinensis in body morphology, pigmentation and head spination.

Occurrence of Cryptosporidium parvum and Bacterial Pathogens in Faecal Material in the Red Fox (Vulpes vulpes) Population - Y. Nagano; M. B. Finn; C. J. Lowery; T. Murphy; J. Moriarty; E. Power; D. Toolan; A. O’Loughlin; M. Watabe; K. A. McCorry; E. Crothers; J. S. G. Dooley; et al. (Veterinary Research Communications, 2007)

Large-Scale Automated Analysis of Location Patterns in Randomly Tagged 3T3 Cells - Elvira García Osuna; Juchang Hua; Nicholas W. Bateman; Ting Zhao; Peter B. Berget; Robert F. Murphy (Annals of Biomedical Engineering, 2007)

Altered cortical integration of dual somatosensory input following the cessation of a 20 min period of repetitive muscle activity - Heidi Haavik Taylor; B. A. Murphy (Experimental Brain Research, 2007)

Production of endothelial nitric oxide synthase (eNOS) over-expressing piglets - Y. H. Hao; H. Y. Yong; C. N. Murphy; D. Wax; M. Samuel; A. Rieke; L. Lai; Z. Liu; D. C. Durtschi; V. R. Welbern; E. M. Price; R. M. McAllister; et al. (Transgenic Research, 2006)

Sediment TCDD-EQs and EROD and MROD Activities in Ranid Frogs from Agricultural and Nonagricultural Sites in Michigan (USA) - M. B. Murphy; M. Hecker; K. K. Coady; A. R. Tompsett; P. D. Jones; J. L. Newsted; H. L. Wong; L. H. du Preez; K. R. Solomon; J. A. Carr; E. E. Smith; R. J. Kendall; et al. (Archives of Environmental Contamination and Toxicology, 2006)

Frequency distributions of transient regional climate change from perturbed physics ensembles of general circulation model simulations - G. R. Harris; D. M. H. Sexton; B. B. B. Booth; M. Collins; J. M. Murphy; M. J. Webb (Climate Dynamics, 2006)

Towards quantifying uncertainty in transient climate change - Matthew Collins; Ben B. B. Booth; Glen R. Harris; James M. Murphy; David M. H. Sexton; Mark J. Webb (Climate Dynamics, 2006)

Sectioned pelvic fin ray ageing of muskellunge Esox masquinongy from a Virginia river: comparisons among readers, with cleithrum estimates, and with tag–recapture growth data - T. O. BRENDEN; E. M. HALLERMAN; B. R. MURPHY (Fisheries Management and Ecology, 2006)
The potential utility of pelvic fin rays as ageing structures was evaluated for southern US muskellunge Esox masquinongy Mitchill populations by comparing age estimates among three readers and against cleithrum estimates, and by comparing observed length changes of tagged fish with changes predicted from growth equations based on pelvic fin ray age estimates. Mean coefficient of variation in age estimates among all readers and between the two readers with prior ageing experience was 17.8% and 5.6%, respectively. Exact and within 1‐year agreement rates between pelvic fin rays and cleithra were 76% and 100%, respectively. Mean (± 2 SE) estimated absolute error between observed and predicted length changes for 13 tagged muskellunge was 30 ± 14 mm. This evaluation indicated that pelvic fin rays may prove to be a useful, non‐lethal method for ageing muskellunge in southern US waters. Validation studies are still needed to ensure that growth rings form consistently throughout fish's life span.

Natal homing in juvenile loggerhead turtles ( Caretta caretta ) - BRIAN W. BOWEN; ANNA L. BASS; SHAIO‐MEI CHOW; MEREDITH BOSTROM; KAREN A. BJORNDAL; ALAN B. BOLTEN; TOSHINORI OKUYAMA; BENJAMIN M. BOLKER; SHERYAN EPPERLY; ERIN LACASELLA; DONNA SHAVER; MARK DODD; et al. (Molecular Ecology, 2004)
Juvenile loggerhead turtles ( Caretta caretta ) from West Atlantic nesting beaches occupy oceanic (pelagic) habitats in the eastern Atlantic and Mediterranean, whereas larger juvenile turtles occupy shallow (neritic) habitats along the continental coastline of North America. Hence the switch from oceanic to neritic stage can involve a trans‐oceanic migration. Several researchers have suggested that at the end of the oceanic phase, juveniles are homing to feeding habitats in the vicinity of their natal rookery. To test the hypothesis of juvenile homing behaviour, we surveyed 10 juvenile feeding zones across the eastern USA with mitochondrial DNA control region sequences ( N = 1437) and compared these samples to potential source (nesting) populations in the Atlantic Ocean and Mediterranean Sea ( N = 465). The results indicated a shallow, but significant, population structure of neritic juveniles (Φ ST = 0.0088, P = 0.016), and haplotype frequency differences were significantly correlated between coastal feeding populations and adjacent nesting populations (Mantel test R 2 = 0.52, P = 0.001). Mixed stock analyses (using a Bayesian algorithm) indicated that juveniles occurred at elevated frequency in the vicinity of their natal rookery. Hence, all lines of evidence supported the hypothesis of juvenile homing in loggerhead turtles. While not as precise as the homing of breeding adults, this behaviour nonetheless places juvenile turtles in the vicinity of their natal nesting colonies. Some of the coastal hazards that affect declining nesting populations may also affect the next generation of turtles feeding in nearby habitats.

The comparative biology of two sympatric paper wasps in Michigan, the native Polistes fuscatus and the invasive Polistes dominulus (Hymenoptera, Vespidae) - G. J. Gamboa; M. A. Noble; M. C. Thom; J. L. Togal; R. Srinivasan; B. D. Murphy (Insectes Sociaux, 2004)

Virology Division News - Frederick A. Murphy; Robert B. Tesh; Charles H. Calisher; David Walker (Archives of Virology, 2004)

Coronary Stent Strut Size Dependent Stress–Strain Response Investigated Using Micromechanical Finite Element Models - P. Savage; B. P. O' Donnell; P. E. McHugh; B. P. Murphy; D. F. Quinn (Annals of Biomedical Engineering, 2004)

The Stress–Strain Behavior of Coronary Stent Struts is Size Dependent - B. P. Murphy; P. Savage; P. E. McHugh; D. F. Quinn (Annals of Biomedical Engineering, 2003)

Sequence Analysis of the Washington/1964 strain of Human Parainfluenza Virus Type 1 (HPIV1) and Recovery and Characterization of Wild Type Recombinant HPIV1 Produced by Reverse Genetics - J. T. Newman; S. R. Surman; J. M. Riggs; Chris T. Hansen; P. L. Collins; B. R. Murphy; M.H. Skiadopoulos (Virus Genes, 2003)

A selective somatostatin type-2 receptor agonist inhibits neointimal thickening and enhances endothelial cell growth and morphology following aortic balloon injury in the rabbit - Natali K. Schiller; Alvin M. Timothy; Harmeet S. Aurora; I-Li Chen; David H. Coy; William A. Murphy; Donald L. Akers; Vivian A. Fonseca; Philip J. Kadowitz; Dennis B. McNamara (Molecular and Cellular Biochemistry, 2002)

Using Remote Sensing to Assess Russian Forest Fire Carbon Emissions - A. S. Isaev; G. N. Korovin; S. A. Bartalev; D. V. Ershov; A. Janetos; E. S. Kasischke; H. H. Shugart; N. H. F. French; B. E. Orlick; T. L. Murphy (Climatic Change, 2002)

Nestedness analysis and conservation planning: the importance of place, environment, and life history across taxonomic groups - Erica Fleishman; Christopher J. Betrus; Robert B. Blair; Ralph Mac Nally; Dennis D. Murphy (Oecologia, 2002)

The effects of tryptophan depletion on cognitive and affective processing in healthy volunteers - F. Murphy; K. Smith; P. Cowen; T. Robbins; B. Sahakian (Psychopharmacology, 2002)

Toxic and Feeding Deterrent Effects of Native Aquatic Macrophytes on Exotic Grass Carp (Ctenopharyngodon idella) - Joseph E. Murphy; Kimberlee B. Beckmen; Julie K. Johnson; Rhian B. Cope; Todd Lawmaster; Val R. Beasley (Ecotoxicology, 2002)

Development of Multiplexed Fluorescence Microbead Covalent Assays (FMCAs) for Pesticide Biomonitoring - R. E. Biagini; D. M. Murphy; D. L. Sammons; J. P. Smith; C. A. F. Striley; B. A. MacKenzie (Bulletin of Environmental Contamination and Toxicology, 2002)

Assessment of Risks of Brodifacoum to Non-target Birds and Mammals in New Zealand - Charles T. Eason; Elaine C. Murphy; Geoffrey R.G. Wright; Eric B. Spurr (Ecotoxicology, 2002)

Cloning, sequence analysis and radiation hybrid mapping of a mammalian KRT 2p gene - Amy B. Miller; Jennifer K. Lowe; Elaine A. Ostrander; Francis Galibert; Keith E. Murphy (Functional & Integrative Genomics, 2001)

Prediction of uphill time-trial bicycling performance in humans with a scaling-derived protocol - D. P. Heil; O. F. Murphy; A. R. Mattingly; B. K. Higginson (European Journal of Applied Physiology, 2001)

Post-orogenic exhumation of an auriferous terrane: the paleoplacer potential of the Early Carboniferous St. Marys Basin, Canadian Appalachians - L. C. Jennex; J. B. Murphy; A. J. Anderson (Mineralium Deposita, 2000)

Caleosins: Ca2+-binding proteins associated with lipid bodies - Henrik Næsted; Gitte I. Frandsen; Guang-Yuh Jauh; Immaculada Hernandez-Pinzon; Henrik B. Nielsen; Denis J. Murphy; John C. Rogers; John Mundy (Plant Molecular Biology, 2000)

Measurement of Serum Antigen Concentration by Ultrasound-Enhanced Immunoassay and Correlation with Clinical Outcome in Meningococcal Disease - M. A. Sobanski; R. A. Barnes; S. J. Gray; A. D. Carr; E. B. Kaczmarski; A. O'Rourke; K. Murphy; M. Cafferkey; R. W. Ellis; K. Pidcock; P. Hawtin; W. T. Coakley (European Journal of Clinical Microbiology & Infectious Diseases, 2000)

The use of image analysis to study developmental variation in micropropagated potato (Solanum tuberosum L.) plants - A. C. Cassells; B. Kowalski; D. M. Fitzgerald; G. A. Murphy (Potato Research, 1999)

Combined analysis of field and model data: A case study of the phosphate dynamics in the German Bight in summer 1994 - Th. Pohlmann; Th. Raabe; R. Doerffer; S. Beddig; U. Brockmann; S. Dick; M. Engel; K. -J. Hesse; P. König; B. Mayer; A. Moll; D. Murphy; et al. (Ocean Dynamics, 1999)

SPM concentrations in the German Bight: comparison between a model simulation and measurements - W. Puls; J. Beusekom; U. Brockmann; R. Doerffer; U. Hentschke; P. König; D. Murphy; B. Mayer; A. Müller; Th. Pohlmann; A. Reimer; R. Schmidt-Nia; et al. (Ocean Dynamics, 1999)

Chromosomal localization of acidic and basic keratin genes of the domestic dog - Amy B. Miller; Matthew Breen; Keith E. Murphy (Mammalian Genome, 1999)

Delayed obsessive-compulsive disorder symptom exacerbation after a single dose of a serotonin antagonist in fluoxetine-treated but not untreated patients - B. D. Greenberg; Jonathan Benjamin; Juliet D. Martin; David Keuler; S.-J. Huang; Margaret Altemus; Dennis L. Murphy (Psychopharmacology, 1998)

Genotype/phenotype correlation in affected individuals of a family with a deletion of the entire coding sequence of the connexin 32 gene - P. J. Ainsworth; C. F. Bolton; B. C. Murphy; J. A. Stuart; A. F. Hahn (Human Genetics, 1998)

Abstracts of papers presented at an international workshop on management of soilborne pathogens sponsored by the United States-Israel binational agricultural research and development fund (bard) - R. J. Cook; J. Katan; I. Chet; J. Katan; R. Rodriguez-Kabana; C. R. Taylor; J. W. Kloepper; M. M. Satour; G. L. Lazarovits; K. L. Conn; M. Tenuta; G. Kritzman; et al. (Phytoparasitica, 1998)

Activation of neurokinin 1 receptors on interstitial cells of Cajal of the guinea-pig small intestine by substance P - S. T. Lavin; B. R. Southwell; R. Murphy; K. M. Jenkinson; J. B. Furness (Histochemistry and Cell Biology, 1998)

Treatment of Urban Areas within a Regional Transport Model of Sulphur and Nitrogen Oxides - E. Murphy-Klimova; B. E. A. Fisher; R. Sokhi (Environmental Monitoring and Assessment, 1998)

Influence of natural variability and the cold start problem on the simulated transient response to increasing CO 2 - A. B. Keen; J. M. Murphy (Climate Dynamics, 1997)

Does Salicylic Acid Act as a Signal in Cotton for Induced Resistance to Helicoverpa zea? - J. L. BI; J. B. Murphy; G. W. Felton (Journal of Chemical Ecology, 1997)

Antinutritive and Oxidative Components as Mechanisms of Induced Resistance in Cotton to Helicoverpa zea - J. L. Bi; J. B. Murphy; G. W. Felton (Journal of Chemical Ecology, 1997)

SUMMER MOISTURE AVAILABILITY OVER EUROPE IN THE HADLEY CENTRE GENERAL CIRCULATION MODEL BASED ON THE PALMER DROUGHT SEVERITY INDEX - P. D. JONES; M. HULME; K. R. BRIFFA; C. G. JONES; J. F. B. MITCHELL; J. M. MURPHY (International Journal of Climatology, 1996)

The Potato Association of America 75th Annual Meeting Spokane, Washington, U.S.A. - David Curwen; Pete Weingartner; Ronald Knight; Therese M. Work; Hugh J. Murphy; Steven B. Johnson; Richard Zink; Leigh Morrow; A. R. Mosley; Rod Davidson; Thoms Owings; Don Halseth; et al. (American Journal of Potato Research, 1991)

Somerset: A new chipping potato variety - R. H. True; A. F. Reeves; R. V. Akeley; H. J. Murphy; G. A. Porter; R. H. Cole; J. Watts; B. J. Christ; F. E. Manzer (American Journal of Potato Research, 1990)

Electron microscopic and antigenic studies of uncharacterized viruses. II. Evidence suggesting the placement of viruses in the familyBunyaviridae - H. G. Zeller; N. Karabatsos; Ch. H. Calisher; J. -P. Digoutte; C. B. Cropp; F. A. Murphy; R. E. Shope (Archives of Virology, 1989)

Electron microscopic and antigenic studies of uncharacterized viruses. III. Evidence suggesting the placement of viruses in the familyReoviridae - H. G. Zeller; N. Karabatsos; C. H. Calisher; J. -P. Digoutte; C. B. Cropp; F. A. Murphy; R. E. Shope (Archives of Virology, 1989)

Islander: A golden nematode resistant potato variety for fresh market and chipping - A. F. Reeves; R. V. Akeley; F. E. Manzer; H. J. Murphy; R. H. True; J. B. Sieczka; D. D. Moyer (American Journal of Potato Research, 1984)

Yankee Chipper: A new golden nematode resistant potato variety with wide adaptation in the northeastern United States - A. F. Reeves; R. V. Akeley; F. E. Manzer; H. J. Murphy; R. H. True; J. B. Sieczka; D. D. Moyer (American Journal of Potato Research, 1984)

Temperature-sensitive mutants of influenza A virus. Transfer of the twots-1 A 2ts lesions present in the Udorn/72-ts-1 A 2 donor virus to the influenza A/Alaska/6/77 (H 3 N 2) wild type virus - B. R. Murphy; F. T. Wood; J. G. Massicot; R. M. Chanock (Archives of Virology, 1980)

Temperature-sensitive mutants of influenza A virus: Evaluation of the Alaska/77-ts-1 A 2 temperature-sensitive recombinant virus in seronegative adult volunteers - B. R. Murphy; R. M. Chanock; R. G. Douglas; R. F. Betts; D. H. Waterman; H. P. Holley; D. L. Hoover; S. Suwanagool; D. R. Nalin; M. M. Levine (Archives of Virology, 1980)

Probable association of plaque size with neuraminidase subtype among H3N2 influenza A viruses - L. J. Markoff; B. R. Murphy; A. J. Kendal; R. M. Chanock (Archives of Virology, 1979)

Viruses isolated from reptiles: Identification of three new members of the familyRhabdoviridae - T. P. Monath; C. B. Cropp; Christina L. Frazier; F. A. Murphy; Sylvia G. Whitfield (Archives of Virology, 1979)

Host range mutants of an influenza A virus - C. Scholtissek; B. R. Murphy (Archives of Virology, 1978)

Atlantic: A new potato variety with high solids, good processing quality, and resistance to pests - R. E. Webb; D. R. Wilson; J. R. Shumaker; B. Graves; M. R. Henninger; J. Watts; J. A. Frank; H. J. Murphy (American Journal of Potato Research, 1978)

Cold adapted variants of influenza A - S. B. Spring; H. F. Maassab; A. P. Kendal; B. R. Murphy; R. M. Chanock (Archives of Virology, 1977)

s 60th annual meeting The Potato Association of America - R. Kunkel; N. M. Holstad; R. E. Thornton; J. C. Bishop; Herman Timm; V. C. Shekhar; W. M. Iritani; Thornton Robert; Gary Hyde; Malamud Oscar; Robert B. O’Keefe; Mccown Brent; et al. (American Journal of Potato Research, 1976)

s of papers presented at the Fifty-Second Annual Meeting of The Potato Association of America - J. A. Crozier; P. J. Ito; Puente De La Fermin; S. J. Peloquin; P. Severino; E. C. Doll; D. R. Christenson; A. R. Wolcott; Hawkins Arthur; F. D. Howard; Herman Timm; W. J. Flocker; et al. (American Journal of Potato Research, 1968)

s of papers presented at the 50th Anniversary Meeting of The Potato Association of America and 13th National Potato Utilization Conference Perkins Inn, Riverhead, New York July 15, 16, 17, 18, 1963 - Glenn D. Boyd; Calderon Peter; Ora Smith; L. R. Mattick; John C. Campbell; R. C. Cetas; Carl O. Davis; Smith Ora; C. H. Dearborn; F. H. Drazga; R. K. Eskew; F. B. Talley; et al. (American Journal of Potato Research, 1963)

Minutes of Executive Committee Meeting, Annual Business Meeting, Committee reports and Financial Report - L. C. Young; Richard L. Sawyer; Hugh J. Murphy; J. W. Scannell; John C. Campbell; Walter C. Sparks; Ora Smith; William B. Raymer; R. H. Treadway; J. C. Campbell; Arthur Hawkins; R. G. Rowberry; et al. (American Journal of Potato Research, 1962)

s of papers presented at the Forty-Third annual meeting of The Potato Association of America - R. H. Bagnall; D. A. Young; Barrel R. Bienz; G. D. Brill; J. C. Campbell; G. R. Blake; Paul N. Carpenter; George O. Estes; Harold W. Gausman; Harold W. Gausman; Hawkins Arthur; Henning P. Hansen; et al. (American Journal of Potato Research, 1959)

s of papers presented at the Forty-First annual meeting - Jay L. Haddock; Ray D. Jackson; W. O. Harrington; R. L. Olson; W. J. Weston; Mary L. Belote; W. J. Hooker; A. P. Benson; R. W. Hougas; S. J. Poloquin; R. W. Ross; G. V. C. Houghland; et al. (American Journal of Potato Research, 1958)